Neutrophil “plucking” on megakaryocytes drives platelet production and boosts cardiovascular disease - Petzold, Tobias; Zhang, Zhe; Ballesteros, Iván; Saleh, Inas; Polzin, Amin; Thienel, Manuela; Liu, Lulu; Ul Ain, Qurrat; Ehreiser, Vincent; Weber, Christian; Kilani, Badr; Mertsch, Pontus; et al. (Immunity)
Intravascular neutrophils and platelets collaborate in maintaining host integrity, but their interaction can also trigger thrombotic complications. We report here that cooperation between neutrophil and platelet lineages extends to the earliest stages of platelet formation by megakaryocytes in the bone marrow. Using intravital microscopy, we show that neutrophils “plucked” intravascular megakaryocyte extensions, termed proplatelets, to control platelet production. Following CXCR4-CXCL12-dependent migration towards perisinusoidal megakaryocytes, plucking neutrophils actively pulled on proplatelets and triggered myosin light chain and extracellular-signal-regulated kinase activation through reactive oxygen species. By these mechanisms, neutrophils accelerate proplatelet growth and facilitate continuous release of platelets in steady state. Following myocardial infarction, plucking neutrophils drove excessive release of young, reticulated platelets and boosted the risk of recurrent ischemia. Ablation of neutrophil plucking normalized thrombopoiesis and reduced recurrent thrombosis after myocardial infarction and thrombus burden in venous thrombosis. We establish neutrophil plucking as a target to reduce thromboischemic events.
Keywords: Infectious Diseases; Immunology; Immunology and Allergy

Principles of disease defence in organisms, superorganisms and societies - Cremer, Sylvia; Sixt, Michael K (Nature Reviews Immunology)
Social distancing is an effective way to prevent the spread of disease in societies, whereas infection elimination is a key element of organismal immunity. Here, we discuss how the study of social insects such as ants — which form a superorganism of unconditionally cooperative individuals and thus represent a level of organization that is intermediate between a classical society of individuals and an organism of cells — can help to determine common principles of disease defence across levels of organization.
Keywords: Energy Engineering and Power Technology; Fuel Technology

Plan your trip before you leave: The neutrophils’ search-and-run journey - Stopp, Julian A; Sixt, Michael K (Journal of Cell Biology)
Reading, interpreting and crawling along gradients of chemotactic cues is one of the most complex questions in cell biology. In this issue, Georgantzoglou et al. (2022. J. Cell. Biol.https://doi.org/10.1083/jcb.202103207) use in vivo models to map the temporal sequence of how neutrophils respond to an acutely arising gradient of chemoattractant.
Keywords: Cell Biology

WASp triggers mechanosensitive actin patches to facilitate immune cell migration in dense tissues - Gaertner, Florian; Reis-Rodrigues, Patricia; De Vries, Ingrid; Hons, Miroslav; Aguilera, Juan; Riedl, Michael; Leithner, Alexander F; Tasciyan, Saren; Kopf, Aglaja; Merrin, Jack; Zheden, Vanessa; Kaufmann, Walter; et al. (Developmental Cell)
When crawling through the body, leukocytes often traverse tissues that are densely packed with extracellular matrix and other cells, and this raises the question: How do leukocytes overcome compressive mechanical loads? Here, we show that the actin cortex of leukocytes is mechanoresponsive and that this responsiveness requires neither force sensing via the nucleus nor adhesive interactions with a substrate. Upon global compression of the cell body as well as local indentation of the plasma membrane, Wiskott-Aldrich syndrome protein (WASp) assembles into dot-like structures, providing activation platforms for Arp2/3 nucleated actin patches. These patches locally push against the external load, which can be obstructing collagen fibers or other cells, and thereby create space to facilitate forward locomotion. We show in vitro and in vivo that this WASp function is rate limiting for ameboid leukocyte migration in dense but not in loose environments and is required for trafficking through diverse tissues such as skin and lymph nodes.

Role of microenvironment heterogeneity in cancer cell invasion - Tasciyan, Saren
Detachment of the cancer cells from the bulk of the tumor is the first step of metastasis, which is the primary cause of cancer related deaths. It is unclear, which factors contribute to this step. Recent studies indicate a crucial role of the tumor microenvironment in malignant transformation and metastasis. Studying cancer cell invasion and detachments quantitatively in the context of its physiological microenvironment is technically challenging. Especially, precise control of microenvironmental properties in vivo is currently not possible. Here, I studied the role of microenvironment geometry in the invasion and detachment of cancer cells from the bulk with a simplistic and reductionist approach. In this approach, I engineered microfluidic devices to mimic a pseudo 3D extracellular matrix environment, where I was able to quantitatively tune the geometrical configuration of the microenvironment and follow tumor cells with fluorescence live imaging. To aid quantitative analysis I developed a widely applicable software application to automatically analyze and visualize particle tracking data. Quantitative analysis of tumor cell invasion in isotropic and anisotropic microenvironments showed that heterogeneity in the microenvironment promotes faster invasion and more frequent detachment of cells. These observations correlated with overall higher speed of cells at the edge of the bulk of the cells. In heterogeneous microenvironments cells preferentially passed through larger pores, thus invading areas of least resistance and generating finger-like invasive structures. The detachments occurred mostly at the tips of these structures. To investigate the potential mechanism, we established a two dimensional model to simulate active Brownian particles representing the cell nuclei dynamics. These simulations backed our in vitro observations without the need of precise fitting the simulation parameters. Our model suggests the importance of the pore heterogeneity in the direction perpendicular to the orientation of bias field (lateral heterogeneity), which causes the interface roughening.

In vitro reconstitution reveals phosphoinositides as cargo-release factors and activators of the ARF6 GAP ADAP1 - Düllberg, Christian F; Auer, Albert; Canigova, Nikola; Loibl, Katrin; Loose, Martin (PNAS)
The differentiation of cells depends on a precise control of their internal organization, which is the result of a complex dynamic interplay between the cytoskeleton, molecular motors, signaling molecules, and membranes. For example, in the developing neuron, the protein ADAP1 (ADP-ribosylation factor GTPase-activating protein [ArfGAP] with dual pleckstrin homology [PH] domains 1) has been suggested to control dendrite branching by regulating the small GTPase ARF6. Together with the motor protein KIF13B, ADAP1 is also thought to mediate delivery of the second messenger phosphatidylinositol (3,4,5)-trisphosphate (PIP3) to the axon tip, thus contributing to PIP3 polarity. However, what defines the function of ADAP1 and how its different roles are coordinated are still not clear. Here, we studied ADAP1’s functions using in vitro reconstitutions. We found that KIF13B transports ADAP1 along microtubules, but that PIP3 as well as PI(3,4)P2 act as stop signals for this transport instead of being transported. We also demonstrate that these phosphoinositides activate ADAP1’s enzymatic activity to catalyze GTP hydrolysis by ARF6. Together, our results support a model for the cellular function of ADAP1, where KIF13B transports ADAP1 until it encounters high PIP3/PI(3,4)P2 concentrations in the plasma membrane. Here, ADAP1 disassociates from the motor to inactivate ARF6, promoting dendrite branching.

Shape and function of interstitial chemokine CCL21 gradients are independent of heparan sulfates produced by lymphatic endothelium - Vaahtomeri, Kari; Moussion, Christine; Hauschild, Robert; Sixt, Michael K (Frontiers in Immunology)
Gradients of chemokines and growth factors guide migrating cells and morphogenetic processes. Migration of antigen-presenting dendritic cells from the interstitium into the lymphatic system is dependent on chemokine CCL21, which is secreted by endothelial cells of the lymphatic capillary, binds heparan sulfates and forms gradients decaying into the interstitium. Despite the importance of CCL21 gradients, and chemokine gradients in general, the mechanisms of gradient formation are unclear. Studies on fibroblast growth factors have shown that limited diffusion is crucial for gradient formation. Here, we used the mouse dermis as a model tissue to address the necessity of CCL21 anchoring to lymphatic capillary heparan sulfates in the formation of interstitial CCL21 gradients. Surprisingly, the absence of lymphatic endothelial heparan sulfates resulted only in a modest decrease of CCL21 levels at the lymphatic capillaries and did neither affect interstitial CCL21 gradient shape nor dendritic cell migration toward lymphatic capillaries. Thus, heparan sulfates at the level of the lymphatic endothelium are dispensable for the formation of a functional CCL21 gradient.

Engaging the front wheels to drive through fibrous terrain - Gärtner, Florian R; Sixt, Michael K (Developmental Cell)
In this issue of Developmental Cell, Doyle and colleagues identify periodic anterior contraction as a characteristic feature of fibroblasts and mesenchymal cancer cells embedded in 3D collagen gels. This contractile mechanism generates a matrix prestrain required for crawling in fibrous 3D environments.

Sequential and switchable patterning for studying cellular processes under spatiotemporal control - Zisis, Themistoklis; Schwarz, Jan; Balles, Miriam; Kretschmer, Maibritt; Nemethova, Maria; Chait, Remy P; Hauschild, Robert; Lange, Janina; Guet, Calin C; Sixt, Michael K; Zahler, Stefan (ACS Applied Materials and Interfaces)
Attachment of adhesive molecules on cell culture surfaces to restrict cell adhesion to defined areas and shapes has been vital for the progress of in vitro research. In currently existing patterning methods, a combination of pattern properties such as stability, precision, specificity, high-throughput outcome, and spatiotemporal control is highly desirable but challenging to achieve. Here, we introduce a versatile and high-throughput covalent photoimmobilization technique, comprising a light-dose-dependent patterning step and a subsequent functionalization of the pattern via click chemistry. This two-step process is feasible on arbitrary surfaces and allows for generation of sustainable patterns and gradients. The method is validated in different biological systems by patterning adhesive ligands on cell-repellent surfaces, thereby constraining the growth and migration of cells to the designated areas. We then implement a sequential photopatterning approach by adding a second switchable patterning step, allowing for spatiotemporal control over two distinct surface patterns. As a proof of concept, we reconstruct the dynamics of the tip/stalk cell switch during angiogenesis. Our results show that the spatiotemporal control provided by our “sequential photopatterning” system is essential for mimicking dynamic biological processes and that our innovative approach has great potential for further applications in cell science.

Loss of Hem1 disrupts macrophage function and impacts migration, phagocytosis, and integrin-mediated adhesion - Stahnke, Stephanie; Döring, Hermann; Kusch, Charly; de Gorter, David J.J.; Dütting, Sebastian; Guledani, Aleks; Pleines, Irina; Schnoor, Michael; Sixt, Michael K; Geffers, Robert; Rohde, Manfred; Müsken, Mathias; et al. (Current Biology)
Hematopoietic-specific protein 1 (Hem1) is an essential subunit of the WAVE regulatory complex (WRC) in immune cells. WRC is crucial for Arp2/3 complex activation and the protrusion of branched actin filament networks. Moreover, Hem1 loss of function in immune cells causes autoimmune diseases in humans. Here, we show that genetic removal of Hem1 in macrophages diminishes frequency and efficacy of phagocytosis as well as phagocytic cup formation in addition to defects in lamellipodial protrusion and migration. Moreover, Hem1-null macrophages displayed strong defects in cell adhesion despite unaltered podosome formation and concomitant extracellular matrix degradation. Specifically, dynamics of both adhesion and de-adhesion as well as concomitant phosphorylation of paxillin and focal adhesion kinase (FAK) were significantly compromised. Accordingly, disruption of WRC function in non-hematopoietic cells coincided with both defects in adhesion turnover and altered FAK and paxillin phosphorylation. Consistently, platelets exhibited reduced adhesion and diminished integrin αIIbβ3 activation upon WRC removal. Interestingly, adhesion phenotypes, but not lamellipodia formation, were partially rescued by small molecule activation of FAK. A full rescue of the phenotype, including lamellipodia formation, required not only the presence of WRCs but also their binding to and activation by Rac. Collectively, our results uncover that WRC impacts on integrin-dependent processes in a FAK-dependent manner, controlling formation and dismantling of adhesions, relevant for properly grabbing onto extracellular surfaces and particles during cell edge expansion, like in migration or phagocytosis.
Keywords: General Agricultural and Biological Sciences; General Biochemistry; Genetics and Molecular Biology

Dendritic cell actin dynamics control contact duration and priming efficiency at the immunological synapse - Leithner, Alexander F; Altenburger, LM; Hauschild, R; Assen, Frank P; Rottner, K; TEB, Stradal; Diz-Muñoz, A; Stein, JV; Sixt, Michael K (Journal of Cell Biology)
Dendritic cells (DCs) are crucial for the priming of naive T cells and the initiation of adaptive immunity. Priming is initiated at a heterologous cell–cell contact, the immunological synapse (IS). While it is established that F-actin dynamics regulates signaling at the T cell side of the contact, little is known about the cytoskeletal contribution on the DC side. Here, we show that the DC actin cytoskeleton is decisive for the formation of a multifocal synaptic structure, which correlates with T cell priming efficiency. DC actin at the IS appears in transient foci that are dynamized by the WAVE regulatory complex (WRC). The absence of the WRC in DCs leads to stabilized contacts with T cells, caused by an increase in ICAM1-integrin–mediated cell–cell adhesion. This results in lower numbers of activated and proliferating T cells, demonstrating an important role for DC actin in the regulation of immune synapse functionality.

Cul3 regulates cytoskeleton protein homeostasis and cell migration during a critical window of brain development - Morandell, Jasmin; Schwarz, Lena A; Basilico, Bernadette; Tasciyan, Saren; Dimchev, Georgi A; Nicolas, Armel; Sommer, Christoph M; Kreuzinger, Caroline; Dotter, Christoph; Knaus, Lisa; Dobler, Zoe; Cacci, Emanuele; et al. (Nature Communications)
De novo loss of function mutations in the ubiquitin ligase-encoding gene Cullin3 lead to autism spectrum disorder (ASD). In mouse, constitutive haploinsufficiency leads to motor coordination deficits as well as ASD-relevant social and cognitive impairments. However, induction of Cul3 haploinsufficiency later in life does not lead to ASD-relevant behaviors, pointing to an important role of Cul3 during a critical developmental window. Here we show that Cul3 is essential to regulate neuronal migration and, therefore, constitutive Cul3 heterozygous mutant mice display cortical lamination abnormalities. At the molecular level, we found that Cul3 controls neuronal migration by tightly regulating the amount of Plastin3 (Pls3), a previously unrecognized player of neural migration. Furthermore, we found that Pls3 cell-autonomously regulates cell migration by regulating actin cytoskeleton organization, and its levels are inversely proportional to neural migration speed. Finally, we provide evidence that cellular phenotypes associated with autism-linked gene haploinsufficiency can be rescued by transcriptional activation of the intact allele in vitro, offering a proof of concept for a potential therapeutic approach for ASDs.
Keywords: General Biochemistry; Genetics and Molecular Biology

Pathogenic Escherichia coli hijack the host immune response - Tomasek, Kathrin
Bacteria-host interactions represent a continuous trade-off between benefit and risk. Thus, the host immune response is faced with a non-trivial problem – accommodate beneficial commensals and remove harmful pathogens. This is especially difficult as molecular patterns, such as lipopolysaccharide or specific surface organelles such as pili, are conserved in both, commensal and pathogenic bacteria. Type 1 pili, tightly regulated by phase variation, are considered an important virulence factor of pathogenic bacteria as they facilitate invasion into host cells. While invasion represents a de facto passive mechanism for pathogens to escape the host immune response, we demonstrate a fundamental role of type 1 pili as active modulators of the innate and adaptive immune response.

Type 1 piliated uropathogenic Escherichia coli hijack the host immune response by binding to CD14 - Tomasek, Kathrin; Leithner, Alexander F; Glatzová, Ivana; Lukesch, Michael S.; Guet, Calin C; Sixt, Michael K (bioRxiv)
A key attribute of persistent or recurring bacterial infections is the ability of the pathogen to evade the host’s immune response. Many Enterobacteriaceae express type 1 pili, a pre-adapted virulence trait, to invade host epithelial cells and establish persistent infections. However, the molecular mechanisms and strategies by which bacteria actively circumvent the immune response of the host remain poorly understood. Here, we identified CD14, the major co-receptor for lipopolysaccharide detection, on dendritic cells as a previously undescribed binding partner of FimH, the protein located at the tip of the type 1 pilus of Escherichia coli. The FimH amino acids involved in CD14 binding are highly conserved across pathogenic and non-pathogenic strains. Binding of pathogenic bacteria to CD14 lead to reduced dendritic cell migration and blunted expression of co-stimulatory molecules, both rate-limiting factors of T cell activation. While defining an active molecular mechanism of immune evasion by pathogens, the interaction between FimH and CD14 represents a potential target to interfere with persistent and recurrent infections, such as urinary tract infections or Crohn’s disease.

Partial loss of actin nucleator actin-related protein 2/3 activity triggers blebbing in primary T lymphocytes - Obeidy, Peyman; Ju, Lining A.; Oehlers, Stefan H.; Zulkhernain, Nursafwana S.; Lee, Quintin; Galeano Niño, Jorge L.; Kwan, Rain Y.Q.; Tikoo, Shweta; Cavanagh, Lois L.; Mrass, Paulus; Cook, Adam J.L.; Jackson, Shaun P.; et al. (Immunology and Cell Biology)
T lymphocytes utilize amoeboid migration to navigate effectively within complex microenvironments. The precise rearrangement of the actin cytoskeleton required for cellular forward propulsion is mediated by actin regulators, including the actin‐related protein 2/3 (Arp2/3) complex, a macromolecular machine that nucleates branched actin filaments at the leading edge. The consequences of modulating Arp2/3 activity on the biophysical properties of the actomyosin cortex and downstream T cell function are incompletely understood. We report that even a moderate decrease of Arp3 levels in T cells profoundly affects actin cortex integrity. Reduction in total F‐actin content leads to reduced cortical tension and disrupted lamellipodia formation. Instead, in Arp3‐knockdown cells, the motility mode is dominated by blebbing migration characterized by transient, balloon‐like protrusions at the leading edge. Although this migration mode seems to be compatible with interstitial migration in three‐dimensional environments, diminished locomotion kinetics and impaired cytotoxicity interfere with optimal T cell function. These findings define the importance of finely tuned, Arp2/3‐dependent mechanophysical membrane integrity in cytotoxic effector T lymphocyte activities.

Modeling adhesion-independent cell migration - Jankowiak, Gaspard; Peurichard, Diane; Reversat, Anne; Schmeiser, Christian; Sixt, Michael K (Mathematical Models and Methods in Applied Sciences)
A two-dimensional mathematical model for cells migrating without adhesion capabilities is presented and analyzed. Cells are represented by their cortex, which is modeled as an elastic curve, subject to an internal pressure force. Net polymerization or depolymerization in the cortex is modeled via local addition or removal of material, driving a cortical flow. The model takes the form of a fully nonlinear degenerate parabolic system. An existence analysis is carried out by adapting ideas from the theory of gradient flows. Numerical simulations show that these simple rules can account for the behavior observed in experiments, suggesting a possible mechanical mechanism for adhesion-independent motility.

Microtubules control cellular shape and coherence in amoeboid migrating cells - Kopf, Aglaja; Renkawitz, Jörg; Hauschild, Robert; Girkontaite, Irute; Tedford, Kerry; Merrin, Jack; Thorn-Seshold, Oliver; Trauner, Dirk; Häcker, Hans; Fischer, Klaus Dieter; Kiermaier, Eva; Sixt, Michael K (The Journal of Cell Biology)
Cells navigating through complex tissues face a fundamental challenge: while multiple protrusions explore different paths, the cell needs to avoid entanglement. How a cell surveys and then corrects its own shape is poorly understood. Here, we demonstrate that spatially distinct microtubule dynamics regulate amoeboid cell migration by locally promoting the retraction of protrusions. In migrating dendritic cells, local microtubule depolymerization within protrusions remote from the microtubule organizing center triggers actomyosin contractility controlled by RhoA and its exchange factor Lfc. Depletion of Lfc leads to aberrant myosin localization, thereby causing two effects that rate-limit locomotion: (1) impaired cell edge coordination during path finding and (2) defective adhesion resolution. Compromised shape control is particularly hindering in geometrically complex microenvironments, where it leads to entanglement and ultimately fragmentation of the cell body. We thus demonstrate that microtubules can act as a proprioceptive device: they sense cell shape and control actomyosin retraction to sustain cellular coherence.

T cells: Bridge-and-channel commute to the white pulp - Sixt, Michael K; Lämmermann, Tim (Immunity)
In contrast to lymph nodes, the lymphoid regions of the spleen—the white pulp—are located deep within the organ, yielding the trafficking paths of T cells in the white pulp largely invisible. In an intravital microscopy tour de force reported in this issue of Immunity, Chauveau et al. show that T cells perform unidirectional, perivascular migration through the enigmatic marginal zone bridging channels.

Loss of Ena/VASP interferes with lamellipodium architecture, motility and integrin-dependent adhesion - Damiano-Guercio, Julia; Kurzawa, Laëtitia; Müller, Jan; Dimchev, Georgi A; Schaks, Matthias; Nemethova, Maria; Pokrant, Thomas; Brühmann, Stefan; Linkner, Joern; Blanchoin, Laurent; Sixt, Michael K; Rottner, Klemens; et al. (eLife)
Cell migration entails networks and bundles of actin filaments termed lamellipodia and microspikes or filopodia, respectively, as well as focal adhesions, all of which recruit Ena/VASP family members hitherto thought to antagonize efficient cell motility. However, we find these proteins to act as positive regulators of migration in different murine cell lines. CRISPR/Cas9-mediated loss of Ena/VASP proteins reduced lamellipodial actin assembly and perturbed lamellipodial architecture, as evidenced by changed network geometry as well as reduction of filament length and number that was accompanied by abnormal Arp2/3 complex and heterodimeric capping protein accumulation. Loss of Ena/VASP function also abolished the formation of microspikes normally embedded in lamellipodia, but not of filopodia capable of emanating without lamellipodia. Ena/VASP-deficiency also impaired integrin-mediated adhesion accompanied by reduced traction forces exerted through these structures. Our data thus uncover novel Ena/VASP functions of these actin polymerases that are fully consistent with their promotion of cell migration.

The cytoskeletal regulator HEM1 governs B cell development and prevents autoimmunity - Salzer, Elisabeth; Zoghi, Samaneh; Kiss, Máté G.; Kage, Frieda; Rashkova, Christina; Stahnke, Stephanie; Haimel, Matthias; Platzer, René; Caldera, Michael; Ardy, Rico Chandra; Hoeger, Birgit; Block, Jana; et al. (Science Immunology)
The WAVE regulatory complex (WRC) is crucial for assembly of the peripheral branched actin network constituting one of the main drivers of eukaryotic cell migration. Here, we uncover an essential role of the hematopoietic-specific WRC component HEM1 for immune cell development. Germline-encoded HEM1 deficiency underlies an inborn error of immunity with systemic autoimmunity, at cellular level marked by WRC destabilization, reduced filamentous actin, and failure to assemble lamellipodia. Hem1−/− mice display systemic autoimmunity, phenocopying the human disease. In the absence of Hem1, B cells become deprived of extracellular stimuli necessary to maintain the strength of B cell receptor signaling at a level permissive for survival of non-autoreactive B cells. This shifts the balance of B cell fate choices toward autoreactive B cells and thus autoimmunity.

Vascular surveillance by haptotactic blood platelets in inflammation and infection - Nicolai, Leo; Schiefelbein, Karin; Lipsky, Silvia; Leunig, Alexander; Hoffknecht, Marie; Pekayvaz, Kami; Raude, Ben; Marx, Charlotte; Ehrlich, Andreas; Pircher, Joachim; Zhang, Zhe; Saleh, Inas; et al. (Nature Communications)
Breakdown of vascular barriers is a major complication of inflammatory diseases. Anucleate platelets form blood-clots during thrombosis, but also play a crucial role in inflammation. While spatio-temporal dynamics of clot formation are well characterized, the cell-biological mechanisms of platelet recruitment to inflammatory micro-environments remain incompletely understood. Here we identify Arp2/3-dependent lamellipodia formation as a prominent morphological feature of immune-responsive platelets. Platelets use lamellipodia to scan for fibrin(ogen) deposited on the inflamed vasculature and to directionally spread, to polarize and to govern haptotactic migration along gradients of the adhesive ligand. Platelet-specific abrogation of Arp2/3 interferes with haptotactic repositioning of platelets to microlesions, thus impairing vascular sealing and provoking inflammatory microbleeding. During infection, haptotaxis promotes capture of bacteria and prevents hematogenic dissemination, rendering platelets gate-keepers of the inflamed microvasculature. Consequently, these findings identify haptotaxis as a key effector function of immune-responsive platelets.

Phytohormone cytokinin guides microtubule dynamics during cell progression from proliferative to differentiated stage - Montesinos López, Juan C; Abuzeineh, A; Kopf, Aglaja; Juanes Garcia, Alba; Ötvös, Krisztina; Petrášek, J; Sixt, Michael K; Benková, Eva (The Embo Journal)
Cell production and differentiation for the acquisition of specific functions are key features of living systems. The dynamic network of cellular microtubules provides the necessary platform to accommodate processes associated with the transition of cells through the individual phases of cytogenesis. Here, we show that the plant hormone cytokinin fine‐tunes the activity of the microtubular cytoskeleton during cell differentiation and counteracts microtubular rearrangements driven by the hormone auxin. The endogenous upward gradient of cytokinin activity along the longitudinal growth axis in Arabidopsis thaliana roots correlates with robust rearrangements of the microtubule cytoskeleton in epidermal cells progressing from the proliferative to the differentiation stage. Controlled increases in cytokinin activity result in premature re‐organization of the microtubule network from transversal to an oblique disposition in cells prior to their differentiation, whereas attenuated hormone perception delays cytoskeleton conversion into a configuration typical for differentiated cells. Intriguingly, cytokinin can interfere with microtubules also in animal cells, such as leukocytes, suggesting that a cytokinin‐sensitive control pathway for the microtubular cytoskeleton may be at least partially conserved between plant and animal cells.

Cellular locomotion using environmental topography - Reversat, Anne; Gärtner, Florian R; Merrin, Jack; Stopp, Julian A; Tasciyan, Saren; Aguilera Servin, Juan L; De Vries, Ingrid; Hauschild, Robert; Hons, Miroslav; Piel, Matthieu; Callan-Jones, Andrew; Voituriez, Raphael; et al. (Nature)
Eukaryotic cells migrate by coupling the intracellular force of the actin cytoskeleton to the environment. While force coupling is usually mediated by transmembrane adhesion receptors, especially those of the integrin family, amoeboid cells such as leukocytes can migrate extremely fast despite very low adhesive forces1. Here we show that leukocytes cannot only migrate under low adhesion but can also transmit forces in the complete absence of transmembrane force coupling. When confined within three-dimensional environments, they use the topographical features of the substrate to propel themselves. Here the retrograde flow of the actin cytoskeleton follows the texture of the substrate, creating retrograde shear forces that are sufficient to drive the cell body forwards. Notably, adhesion-dependent and adhesion-independent migration are not mutually exclusive, but rather are variants of the same principle of coupling retrograde actin flow to the environment and thus can potentially operate interchangeably and simultaneously. As adhesion-free migration is independent of the chemical composition of the environment, it renders cells completely autonomous in their locomotive behaviour.

Zena Werb (1945-2020): Cell biology in context - Sixt, Michael K; Huttenlocher, Anna (The Journal of Cell Biology)

Patrolling the vascular borders: Platelets in immunity to infection and cancer - Gärtner, Florian R; Massberg, Steffen (Nature Reviews Immunology)
Platelets are small anucleate cellular fragments that are released by megakaryocytes and safeguard vascular integrity through a process termed ‘haemostasis’. However, platelets have important roles beyond haemostasis as they contribute to the initiation and coordination of intravascular immune responses. They continuously monitor blood vessel integrity and tightly coordinate vascular trafficking and functions of multiple cell types. In this way platelets act as ‘patrolling officers of the vascular highway’ that help to establish effective immune responses to infections and cancer. Here we discuss the distinct biological features of platelets that allow them to shape immune responses to pathogens and tumour cells, highlighting the parallels between these responses.

Mechanisms of 3D cell migration - Yamada, KM; Sixt, Michael K (Nature Reviews Molecular Cell Biology)
Cell migration is essential for physiological processes as diverse as development, immune defence and wound healing. It is also a hallmark of cancer malignancy. Thousands of publications have elucidated detailed molecular and biophysical mechanisms of cultured cells migrating on flat, 2D substrates of glass and plastic. However, much less is known about how cells successfully navigate the complex 3D environments of living tissues. In these more complex, native environments, cells use multiple modes of migration, including mesenchymal, amoeboid, lobopodial and collective, and these are governed by the local extracellular microenvironment, specific modalities of Rho GTPase signalling and non- muscle myosin contractility. Migration through 3D environments is challenging because it requires the cell to squeeze through complex or dense extracellular structures. Doing so requires specific cellular adaptations to mechanical features of the extracellular matrix (ECM) or its remodelling. In addition, besides navigating through diverse ECM environments and overcoming extracellular barriers, cells often interact with neighbouring cells and tissues through physical and signalling interactions. Accordingly, cells need to call on an impressively wide diversity of mechanisms to meet these challenges. This Review examines how cells use both classical and novel mechanisms of locomotion as they traverse challenging 3D matrices and cellular environments. It focuses on principles rather than details of migratory mechanisms and draws comparisons between 1D, 2D and 3D migration.

Platelets in host defense: Experimental and clinical insights - Nicolai, Leo; Gärtner, Florian R; Massberg, Steffen (Trends in Immunology)
Platelets are central players in thrombosis and hemostasis but are increasingly recognized as key components of the immune system. They shape ensuing immune responses by recruiting leukocytes, and support the development of adaptive immunity. Recent data shed new light on the complex role of platelets in immunity. Here, we summarize experimental and clinical data on the role of platelets in host defense against bacteria. Platelets bind, contain, and kill bacteria directly; however, platelet proinflammatory effector functions and cross-talk with the coagulation system, can also result in damage to the host (e.g., acute lung injury and sepsis). Novel clinical insights support this dichotomy: platelet inhibition/thrombocytopenia can be either harmful or protective, depending on pathophysiological context. Clinical studies are currently addressing this aspect in greater depth.

Gut homeostasis: Active migration of intestinal epithelial cells in tissue renewal - Kopf, Aglaja; Sixt, Michael K (Current Biology)

Persistent and polarized global actin flow is essential for directionality during cell migration - Yolland, Lawrence; Burki, Mubarik; Marcotti, Stefania; Luchici, Andrei; Kenny, Fiona N.; Davis, John Robert; Serna-Morales, Eduardo; Müller, Jan; Sixt, Michael K; Davidson, Andrew; Wood, Will; Schumacher, Linus J.; et al. (Nature Cell Biology)
Cell migration is hypothesized to involve a cycle of behaviours beginning with leading edge extension. However, recent evidence suggests that the leading edge may be dispensable for migration, raising the question of what actually controls cell directionality. Here, we exploit the embryonic migration of Drosophila macrophages to bridge the different temporal scales of the behaviours controlling motility. This approach reveals that edge fluctuations during random motility are not persistent and are weakly correlated with motion. In contrast, flow of the actin network behind the leading edge is highly persistent. Quantification of actin flow structure during migration reveals a stable organization and asymmetry in the cell-wide flowfield that strongly correlates with cell directionality. This organization is regulated by a gradient of actin network compression and destruction, which is controlled by myosin contraction and cofilin-mediated disassembly. It is this stable actin-flow polarity, which integrates rapid fluctuations of the leading edge, that controls inherent cellular persistence.

GGA2 and RAB13 promote activity-dependent β1-integrin recycling - Sahgal, Pranshu; Alanko, Jonna H; Icha, Jaroslav; Paatero, Ilkka; Hamidi, Hellyeh; Arjonen, Antti; Pietilä, Mika; Rokka, Anne; Ivaska, Johanna (Journal of Cell Science)
β1-integrins mediate cell–matrix interactions and their trafficking is important in the dynamic regulation of cell adhesion, migration and malignant processes, including cancer cell invasion. Here, we employ an RNAi screen to characterize regulators of integrin traffic and identify the association of Golgi-localized gamma ear-containing Arf-binding protein 2 (GGA2) with β1-integrin, and its role in recycling of active but not inactive β1-integrin receptors. Silencing of GGA2 limits active β1-integrin levels in focal adhesions and decreases cancer cell migration and invasion, which is in agreement with its ability to regulate the dynamics of active integrins. By using the proximity-dependent biotin identification (BioID) method, we identified two RAB family small GTPases, i.e. RAB13 and RAB10, as novel interactors of GGA2. Functionally, RAB13 silencing triggers the intracellular accumulation of active β1-integrin, and reduces integrin activity in focal adhesions and cell migration similarly to GGA2 depletion, indicating that both facilitate active β1-integrin recycling to the plasma membrane. Thus, GGA2 and RAB13 are important specificity determinants for integrin activity-dependent traffic.

Transient localization of the Arp2/3 complex initiates neuronal dendrite branching in vivo - Stürner, Tomke; Tatarnikova, Anastasia; Müller, Jan; Schaffran, Barbara; Cuntz, Hermann; Zhang, Yun; Nemethova, Maria; Bogdan, Sven; Small, Vic; Tavosanis, Gaia (Development)
The formation of neuronal dendrite branches is fundamental for the wiring and function of the nervous system. Indeed, dendrite branching enhances the coverage of the neuron's receptive field and modulates the initial processing of incoming stimuli. Complex dendrite patterns are achieved in vivo through a dynamic process of de novo branch formation, branch extension and retraction. The first step towards branch formation is the generation of a dynamic filopodium-like branchlet. The mechanisms underlying the initiation of dendrite branchlets are therefore crucial to the shaping of dendrites. Through in vivo time-lapse imaging of the subcellular localization of actin during the process of branching of Drosophila larva sensory neurons, combined with genetic analysis and electron tomography, we have identified the Actin-related protein (Arp) 2/3 complex as the major actin nucleator involved in the initiation of dendrite branchlet formation, under the control of the activator WAVE and of the small GTPase Rac1. Transient recruitment of an Arp2/3 component marks the site of branchlet initiation in vivo. These data position the activation of Arp2/3 as an early hub for the initiation of branchlet formation.

Lymph node mechanics: Deciphering the interplay between stroma contractility, morphology and lymphocyte trafficking - Assen, Frank P
Lymph nodes are es s ential organs of the immune s ys tem where adaptive immune responses originate, and consist of various leukocyte populations and a stromal backbone. Fibroblastic reticular cells (FRCs) are the main stromal cells and form a sponge-like extracellular matrix network, called conduits , which they thems elves enwrap and contract. Lymph, containing s oluble antigens , arrive in lymph nodes via afferent lymphatic vessels that connect to the s ubcaps ular s inus and conduit network. According to the current paradigm, the conduit network dis tributes afferent lymph through lymph nodes and thus provides acces s for immune cells to lymph-borne antigens. An elas tic caps ule s urrounds the organ and confines the immune cells and FRC network. Lymph nodes are completely packed with lymphocytes and lymphocyte numbers directly dictates the size of the organ. Although lymphocytes cons tantly enter and leave the lymph node, its s ize remains remarkedly s table under homeostatic conditions. It is only partly known how the cellularity and s ize of the lymph node is regulated and how the lymph node is able to swell in inflammation. The role of the FRC network in lymph node s welling and trans fer of fluids are inves tigated in this thes is. Furthermore, we s tudied what trafficking routes are us ed by cancer cells in lymph nodes to form distal metastases.We examined the role of a mechanical feedback in regulation of lymph node swelling. Using parallel plate compression and UV-las er cutting experiments we dis s ected the mechanical force dynamics of the whole lymph node, and individually for FRCs and the caps ule. Physical forces generated by packed lymphocytes directly affect the tens ion on the FRC network and capsule, which increases its resistance to swelling. This implies a feedback mechanism between tis s ue pres s ure and ability of lymphocytes to enter the organ. Following inflammation, the lymph node swells ∼10 fold in two weeks . Yet, what is the role for tens ion on the FRC network and caps ule, and how are lymphocytes able to enter in conditions that resist swelling remain open ques tions . We s how that tens ion on the FRC network is important to limit the swelling rate of the organ so that the FRC network can grow in a coordinated fashion. This is illustrated by interfering with FRC contractility, which leads to faster swelling rates and a dis organized FRC network in the inflamed lymph node. Growth of the FRC network in turn is expected to releas e tens ion on thes e s tructures and lowers the res is tance to swelling, thereby allowing more lymphocytes to enter the organ and drive more swelling. Halt of swelling coincides with a thickening of the caps ule, which forms a thick res is tant band around the organ and lowers tens ion on the FRC network to form a new force equilibrium.The FRC and conduit network are further believed to be a privileged s ite of s oluble information within the lymph node, although many details remain uns olved. We s how by 3D ultra-recons truction that FRCs and antigen pres enting cells cover the s urface of conduit s ys tem for more than 99% and we dis cus s the implications for s oluble information exchangeat the conduit level.Finally, there is an ongoing debate in the cancer field whether and how cancer cells in lymph nodes s eed dis tal metas tas es . We s how that cancer cells infus ed into the lymph node can utilize trafficking routes of immune cells and rapidly migrate to blood vessels. Once in the blood circulation, these cells are able to form metastases in distal tissues.

The implication of cytoskeletal dynamics on leukocyte migration - Kopf, Aglaja
While cells of mesenchymal or epithelial origin perform their effector functions in a purely anchorage dependent manner, cells derived from the hematopoietic lineage are not committed to operate only within a specific niche. Instead, these cells are able to function autonomously of the molecular composition in a broad range of tissue compartments. By this means, cells of the hematopoietic lineage retain the capacity to disseminate into connective tissue and recirculate between organs, building the foundation for essential processes such as tissue regeneration or immune surveillance. Cells of the immune system, specifically leukocytes, are extraordinarily good at performing this task. These cells are able to flexibly shift their mode of migration between an adhesion-mediated and an adhesion-independent manner, instantaneously accommodating for any changes in molecular composition of the external scaffold. The key component driving directed leukocyte migration is the chemokine receptor 7, which guides the cell along gradients of chemokine ligand. Therefore, the physical destination of migrating leukocytes is purely deterministic, i.e. given by global directional cues such as chemokine gradients. Nevertheless, these cells typically reside in three-dimensional scaffolds of inhomogeneous complexity, raising the question whether cells are able to locally discriminate between multiple optional migration routes. Current literature provides evidence that leukocytes, specifically dendritic cells, do indeed probe their surrounding by virtue of multiple explorative protrusions. However, it remains enigmatic how these cells decide which one is the more favorable route to follow and what are the key players involved in performing this task. Due to the heterogeneous environment of most tissues, and the vast adaptability of migrating leukocytes, at this time it is not clear to what extent leukocytes are able to optimize their migratory strategy by adapting their level of adhesiveness. And, given the fact that leukocyte migration is characterized by branched cell shapes in combination with high migration velocities, it is reasonable to assume that these cells require fine tuned shape maintenance mechanisms that tightly coordinate protrusion and adhesion dynamics in a spatiotemporal manner. Therefore, this study aimed to elucidate how rapidly migrating leukocytes opt for an ideal migratory path while maintaining a continuous cell shape and balancing adhesive forces to efficiently navigate through complex microenvironments. The results of this study unraveled a role for the microtubule cytoskeleton in promoting the decision making process during path finding and for the first time point towards a microtubule-mediated function in cell shape maintenance of highly ramified cells such as dendritic cells. Furthermore, we found that migrating low-adhesive leukocytes are able to instantaneously adapt to increased tensile load by engaging adhesion receptors. This response was only occurring tangential to the substrate while adhesive properties in the vertical direction were not increased. As leukocytes are primed for rapid migration velocities, these results demonstrate that leukocyte integrins are able to confer a high level of traction forces parallel to the cell membrane along the direction of migration without wasting energy in gluing the cell to the substrate. Thus, the data in the here presented thesis provide new insights into the pivotal role of cytoskeletal dynamics and the mechanisms of force transduction during leukocyte migration. Thereby the here presented results help to further define fundamental principles underlying leukocyte migration and open up potential therapeutic avenues of clinical relevance.
Keywords: cell biology; immunology; leukocyte; migration; microfluidics

Nuclear positioning facilitates amoeboid migration along the path of least resistance - Renkawitz, Jörg; Kopf, Aglaja; Stopp, Julian A; de Vries, Ingrid; Driscoll, Meghan K.; Merrin, Jack; Hauschild, Robert; Welf, Erik S.; Danuser, Gaudenz; Fiolka, Reto; Sixt, Michael K (Nature)
During metazoan development, immune surveillance and cancer dissemination, cells migrate in complex three-dimensional microenvironments1,2,3. These spaces are crowded by cells and extracellular matrix, generating mazes with differently sized gaps that are typically smaller than the diameter of the migrating cell4,5. Most mesenchymal and epithelial cells and some—but not all—cancer cells actively generate their migratory path using pericellular tissue proteolysis6. By contrast, amoeboid cells such as leukocytes use non-destructive strategies of locomotion7, raising the question how these extremely fast cells navigate through dense tissues. Here we reveal that leukocytes sample their immediate vicinity for large pore sizes, and are thereby able to choose the path of least resistance. This allows them to circumnavigate local obstacles while effectively following global directional cues such as chemotactic gradients. Pore-size discrimination is facilitated by frontward positioning of the nucleus, which enables the cells to use their bulkiest compartment as a mechanical gauge. Once the nucleus and the closely associated microtubule organizing centre pass the largest pore, cytoplasmic protrusions still lingering in smaller pores are retracted. These retractions are coordinated by dynamic microtubules; when microtubules are disrupted, migrating cells lose coherence and frequently fragment into migratory cytoplasmic pieces. As nuclear positioning in front of the microtubule organizing centre is a typical feature of amoeboid migration, our findings link the fundamental organization of cellular polarity to the strategy of locomotion.

The neural crest pitches in to remove apoptotic debris - Kopf, Aglaja; Sixt, Michael K (Cell)

Platelet migration and bacterial trapping assay under flow - Fan, Shuxia; Lorenz, Michael; Massberg, Steffen; Gärtner, Florian R (Bio-Protocol)
Blood platelets are critical for hemostasis and thrombosis, but also play diverse roles during immune responses. We have recently reported that platelets migrate at sites of infection in vitro and in vivo. Importantly, platelets use their ability to migrate to collect and bundle fibrin (ogen)-bound bacteria accomplishing efficient intravascular bacterial trapping. Here, we describe a method that allows analyzing platelet migration in vitro, focusing on their ability to collect bacteria and trap bacteria under flow.
Keywords: Platelets; Cell migration; Bacteria; Shear flow; Fibrinogen; E. coli

A fat lot of good for wound healing - Casano, Alessandra M; Sixt, Michael K (Developmental Cell)
The insect’s fat body combines metabolic and immunological functions. In this issue of Developmental Cell, Franz et al. (2018) show that in Drosophila, cells of the fat body are not static, but can actively “swim” toward sites of epithelial injury, where they physically clog the wound and locally secrete antimicrobial peptides.

Drosophila TNF modulates tissue tension in the embryo to facilitate macrophage invasive migration - Ratheesh, Aparna; Biebl, Julia; Smutny, Michael; Veselá, Jana; Papusheva, Ekaterina; Krens, Gabriel; Kaufmann, Walter; György, Attila; Casano, Alessandra M; Siekhaus, Daria E (Developmental Cell)
Migrating cells penetrate tissue barriers during development, inflammatory responses, and tumor metastasis. We study if migration in vivo in such three-dimensionally confined environments requires changes in the mechanical properties of the surrounding cells using embryonic Drosophila melanogaster hemocytes, also called macrophages, as a model. We find that macrophage invasion into the germband through transient separation of the apposing ectoderm and mesoderm requires cell deformations and reductions in apical tension in the ectoderm. Interestingly, the genetic pathway governing these mechanical shifts acts downstream of the only known tumor necrosis factor superfamily member in Drosophila, Eiger, and its receptor, Grindelwald. Eiger-Grindelwald signaling reduces levels of active Myosin in the germband ectodermal cortex through the localization of a Crumbs complex component, Patj (Pals-1-associated tight junction protein). We therefore elucidate a distinct molecular pathway that controls tissue tension and demonstrate the importance of such regulation for invasive migration in vivo.

Fast and efficient genetic engineering of hematopoietic precursor cells for the study of dendritic cell migration - Leithner, Alexander F; Renkawitz, Jörg; De Vries, Ingrid; Hauschild, Robert; Haecker, Hans; Sixt, Michael K (European Journal of Immunology)
Dendritic cells (DCs) are sentinels of the adaptive immune system that reside in peripheral organs of mammals. Upon pathogen encounter, they undergo maturation and up-regulate the chemokine receptor CCR7 that guides them along gradients of its chemokine ligands CCL19 and 21 to the next draining lymph node. There, DCs present peripherally acquired antigen to naïve T cells, thereby triggering adaptive immunity.

IgM's exit route - Reversat, Anne; Sixt, Michael K (Journal of Experimental Medicine)
The release of IgM is the first line of an antibody response and precedes the generation of high affinity IgG in germinal centers. Once secreted by freshly activated plasmablasts, IgM is released into the efferent lymph of reactive lymph nodes as early as 3 d after immunization. As pentameric IgM has an enormous size of 1,000 kD, its diffusibility is low, and one might wonder how it can pass through the densely lymphocyte-packed environment of a lymph node parenchyma in order to reach its exit. In this issue of JEM, Thierry et al. show that, in order to reach the blood stream, IgM molecules take a specific micro-anatomical route via lymph node conduits.

Lymphatic exosomes promote dendritic cell migration along guidance cues - Brown, Markus; Johnson, Louise; Leone, Dario; Májek, Peter; Vaahtomeri, Kari; Senfter, Daniel; Bukosza, Nora; Schachner, Helga; Asfour, Gabriele; Langer, Brigitte; Hauschild, Robert; Parapatics, Katja; et al. (Journal of Cell Biology)
Lymphatic endothelial cells (LECs) release extracellular chemokines to guide the migration of dendritic cells. In this study, we report that LECs also release basolateral exosome-rich endothelial vesicles (EEVs) that are secreted in greater numbers in the presence of inflammatory cytokines and accumulate in the perivascular stroma of small lymphatic vessels in human chronic inflammatory diseases. Proteomic analyses of EEV fractions identified > 1,700 cargo proteins and revealed a dominant motility-promoting protein signature. In vitro and ex vivo EEV fractions augmented cellular protrusion formation in a CX3CL1/fractalkine-dependent fashion and enhanced the directional migratory response of human dendritic cells along guidance cues. We conclude that perilymphatic LEC exosomes enhance exploratory behavior and thus promote directional migration of CX3CR1-expressing cells in complex tissue environments.

Mechanistic description of spatial processes using integrative modelling of noise-corrupted imaging data - Hross, Sabrina; Theis, Fabian J.; Sixt, Michael K; Hasenauer, Jan (Journal of the Royal Society Interface)
Spatial patterns are ubiquitous on the subcellular, cellular and tissue level, and can be studied using imaging techniques such as light and fluorescence microscopy. Imaging data provide quantitative information about biological systems; however, mechanisms causing spatial patterning often remain elusive. In recent years, spatio-temporal mathematical modelling has helped to overcome this problem. Yet, outliers and structured noise limit modelling of whole imaging data, and models often consider spatial summary statistics. Here, we introduce an integrated data-driven modelling approach that can cope with measurement artefacts and whole imaging data. Our approach combines mechanistic models of the biological processes with robust statistical models of the measurement process. The parameters of the integrated model are calibrated using a maximum-likelihood approach. We used this integrated modelling approach to study in vivo gradients of the chemokine (C-C motif) ligand 21 (CCL21). CCL21 gradients guide dendritic cells and are important in the adaptive immune response. Using artificial data, we verified that the integrated modelling approach provides reliable parameter estimates in the presence of measurement noise and that bias and variance of these estimates are reduced compared to conventional approaches. The application to experimental data allowed the parametrization and subsequent refinement of the model using additional mechanisms. Among other results, model-based hypothesis testing predicted lymphatic vessel-dependent concentration of heparan sulfate, the binding partner of CCL21. The selected model provided an accurate description of the experimental data and was partially validated using published data. Our findings demonstrate that integrated statistical modelling of whole imaging data is computationally feasible and can provide novel biological insights.

Micro-engineered “pillar forests” to study cell migration in complex but controlled 3D environments - Renkawitz, Jörg; Reversat, Anne; Leithner, Alexander F; Merrin, Jack; Sixt, Michael K (Methods in Cell Biology)
Cells migrating in multicellular organisms steadily traverse complex three-dimensional (3D) environments. To decipher the underlying cell biology, current experimental setups either use simplified 2D, tissue-mimetic 3D (e.g., collagen matrices) or in vivo environments. While only in vivo experiments are truly physiological, they do not allow for precise manipulation of environmental parameters. 2D in vitro experiments do allow mechanical and chemical manipulations, but increasing evidence demonstrates substantial differences of migratory mechanisms in 2D and 3D. Here, we describe simple, robust, and versatile “pillar forests” to investigate cell migration in complex but fully controllable 3D environments. Pillar forests are polydimethylsiloxane-based setups, in which two closely adjacent surfaces are interconnected by arrays of micrometer-sized pillars. Changing the pillar shape, size, height and the inter-pillar distance precisely manipulates microenvironmental parameters (e.g., pore sizes, micro-geometry, micro-topology), while being easily combined with chemotactic cues, surface coatings, diverse cell types and advanced imaging techniques. Thus, pillar forests combine the advantages of 2D cell migration assays with the precise definition of 3D environmental parameters.

Nano-scale microfluidics to study 3D chemotaxis at the single cell level - Frick, Corina; Dettinger, Philip; Renkawitz, Jörg; Jauch, Annaïse; Berger, Christoph; Recher, Mike; Schroeder, Timm; Mehling, Matthias (PLoS One)
Directed migration of cells relies on their ability to sense directional guidance cues and to interact with pericellular structures in order to transduce contractile cytoskeletal- into mechanical forces. These biomechanical processes depend highly on microenvironmental factors such as exposure to 2D surfaces or 3D matrices. In vivo, the majority of cells are exposed to 3D environments. Data on 3D cell migration are mostly derived from intravital microscopy or collagen-based in vitro assays. Both approaches offer only limited controlla-bility of experimental conditions. Here, we developed an automated microfluidic system that allows positioning of cells in 3D microenvironments containing highly controlled diffusion-based chemokine gradients. Tracking migration in such gradients was feasible in real time at the single cell level. Moreover, the setup allowed on-chip immunocytochemistry and thus linking of functional with phenotypical properties in individual cells. Spatially defined retrieval of cells from the device allows down-stream off-chip analysis. Using dendritic cells as a model, our setup specifically allowed us for the first time to quantitate key migration characteristics of cells exposed to identical gradients of the chemokine CCL19 yet placed on 2D vs in 3D environments. Migration properties between 2D and 3D migration were distinct. Morphological features of cells migrating in an in vitro 3D environment were similar to those of cells migrating in animal tissues, but different from cells migrating on a surface. Our system thus offers a highly controllable in vitro-mimic of a 3D environment that cells traffic in vivo.

The cell sets the tone - Alanko, Jonna H; Sixt, Michael K (eLife)
In zebrafish larvae, it is the cell type that determines how the cell responds to a chemokine signal.

Optical functionalization of human class A orphan G-protein-coupled receptors - Morri, Maurizio; Sanchez-Romero, Inmaculada; Tichy, Alexandra-Madelaine; Kainrath, Stephanie; Gerrard, Elliot J.; Hirschfeld, Priscila; Schwarz, Jan; Janovjak, Harald L (Nature Communications)
G-protein-coupled receptors (GPCRs) form the largest receptor family, relay environmental stimuli to changes in cell behavior and represent prime drug targets. Many GPCRs are classified as orphan receptors because of the limited knowledge on their ligands and coupling to cellular signaling machineries. Here, we engineer a library of 63 chimeric receptors that contain the signaling domains of human orphan and understudied GPCRs functionally linked to the light-sensing domain of rhodopsin. Upon stimulation with visible light, we identify activation of canonical cell signaling pathways, including cAMP-, Ca2+-, MAPK/ERK-, and Rho-dependent pathways, downstream of the engineered receptors. For the human pseudogene GPR33, we resurrect a signaling function that supports its hypothesized role as a pathogen entry site. These results demonstrate that substituting unknown chemical activators with a light switch can reveal information about protein function and provide an optically controlled protein library for exploring the physiology and therapeutic potential of understudied GPCRs.

On the relation between filament density, force generation, and protrusion rate in mesenchymal cell motility - Dolati, Setareh; Kage, Frieda; Mueller, Jan; Müsken, Mathias; Kirchner, Marieluise; Dittmar, Gunnar; Sixt, Michael K; Rottner, Klemens; Falcke, Martin (Molecular Biology of the Cell)
Lamellipodia are flat membrane protrusions formed during mesenchymal motion. Polymerization at the leading edge assembles the actin filament network and generates protrusion force. How this force is supported by the network and how the assembly rate is shared between protrusion and network retrograde flow determines the protrusion rate. We use mathematical modeling to understand experiments changing the F-actin density in lamellipodia of B16-F1 melanoma cells by modulation of Arp2/3 complex activity or knockout of the formins FMNL2 and FMNL3. Cells respond to a reduction of density with a decrease of protrusion velocity, an increase in the ratio of force to filament number, but constant network assembly rate. The relation between protrusion force and tension gradient in the F-actin network and the density dependency of friction, elasticity, and viscosity of the network explain the experimental observations. The formins act as filament nucleators and elongators with differential rates. Modulation of their activity suggests an effect on network assembly rate. Contrary to these expectations, the effect of changes in elongator composition is much weaker than the consequences of the density change. We conclude that the force acting on the leading edge membrane is the force required to drive F-actin network retrograde flow.

The Rho regulator Myosin IXb enables nonlymphoid tissue seeding of protective CD8+T cells - Moalli, Federica; Ficht, Xenia; Germann, Philipp; Vladymyrov, Mykhailo; Stolp, Bettina; de Vries, Ingrid; Lyck, Ruth; Balmer, Jasmin; Fiocchi, Amleto; Kreutzfeldt, Mario; Merkler, Doron; Iannacone, Matteo; et al. (The Journal of Experimental Medicine)
T cells are actively scanning pMHC-presenting cells in lymphoid organs and nonlymphoid tissues (NLTs) with divergent topologies and confinement. How the T cell actomyosin cytoskeleton facilitates this task in distinct environments is incompletely understood. Here, we show that lack of Myosin IXb (Myo9b), a negative regulator of the small GTPase Rho, led to increased Rho-GTP levels and cell surface stiffness in primary T cells. Nonetheless, intravital imaging revealed robust motility of Myo9b−/− CD8+ T cells in lymphoid tissue and similar expansion and differentiation during immune responses. In contrast, accumulation of Myo9b−/− CD8+ T cells in NLTs was strongly impaired. Specifically, Myo9b was required for T cell crossing of basement membranes, such as those which are present between dermis and epidermis. As consequence, Myo9b−/− CD8+ T cells showed impaired control of skin infections. In sum, we show that Myo9b is critical for the CD8+ T cell adaptation from lymphoid to NLT surveillance and the establishment of protective tissue–resident T cell populations.

Lymph node blood vessels provide exit routes for metastatic tumor cell dissemination in mice - Brown, Markus; Assen, Frank P; Leithner, Alexander F; Abe, Jun; Schachner, Helga; Asfour, Gabriele; Bagó Horváth, Zsuzsanna; Stein, Jens; Uhrin, Pavel; Sixt, Michael K; Kerjaschki, Dontscho (Science)
During metastasis, malignant cells escape the primary tumor, intravasate lymphatic vessels, and reach draining sentinel lymph nodes before they colonize distant organs via the blood circulation. Although lymph node metastasis in cancer patients correlates with poor prognosis, evidence is lacking as to whether and how tumor cells enter the bloodstream via lymph nodes. To investigate this question, we delivered carcinoma cells into the lymph nodes of mice by microinfusing the cells into afferent lymphatic vessels. We found that tumor cells rapidly infiltrated the lymph node parenchyma, invaded blood vessels, and seeded lung metastases without involvement of the thoracic duct. These results suggest that the lymph node blood vessels can serve as an exit route for systemic dissemination of cancer cells in experimental mouse models. Whether this form of tumor cell spreading occurs in cancer patients remains to be determined.

Branched actin networks in dendritic cell biology - Leithner, Alexander F
In the here presented thesis, we explore the role of branched actin networks in cell migration and antigen presentation, the two most relevant processes in dendritic cell biology. Branched actin networks construct lamellipodial protrusions at the leading edge of migrating cells. These are typically seen as adhesive structures, which mediate force transduction to the extracellular matrix that leads to forward locomotion. We ablated Arp2/3 nucleation promoting factor WAVE in DCs and found that the resulting cells lack lamellipodial protrusions. Instead, depending on the maturation state, one or multiple filopodia were formed. By challenging these cells in a variety of migration assays we found that lamellipodial protrusions are dispensable for the locomotion of leukocytes and actually dampen the speed of migration. However, lamellipodia are critically required to negotiate complex environments that DCs experience while they travel to the next draining lymph node. Taken together our results suggest that leukocyte lamellipodia have rather a sensory- than a force transducing function. Furthermore, we show for the first time structure and dynamics of dendritic cell F-actin at the immunological synapse with naïve T cells. Dendritic cell F-actin appears as dynamic foci that are nucleated by the Arp2/3 complex. WAVE ablated dendritic cells show increased membrane tension, leading to an altered ultrastructure of the immunological synapse and severe T cell priming defects. These results point towards a previously unappreciated role of the cellular mechanics of dendritic cells in T cell activation. Additionally, we present a novel cell culture based system for the differentiation of dendritic cells from conditionally immortalized hematopoietic precursors. These precursor cells are genetically tractable via the CRISPR/Cas9 system while they retain their ability to differentiate into highly migratory dendritic cells and other immune cells. This will foster the study of all aspects of dendritic cell biology and beyond.

Chemokines and integrins independently tune actin flow and substrate friction during intranodal migration of T cells - Hons, Miroslav; Kopf, Aglaja; Hauschild, Robert; Leithner, Alexander F; Gärtner, Florian R; Abe, Jun; Renkawitz, Jörg; Stein, Jens; Sixt, Michael K (Nature Immunology)
Although much is known about the physiological framework of T cell motility, and numerous rate-limiting molecules have been identified through loss-of-function approaches, an integrated functional concept of T cell motility is lacking. Here, we used in vivo precision morphometry together with analysis of cytoskeletal dynamics in vitro to deconstruct the basic mechanisms of T cell migration within lymphatic organs. We show that the contributions of the integrin LFA-1 and the chemokine receptor CCR7 are complementary rather than positioned in a linear pathway, as they are during leukocyte extravasation from the blood vasculature. Our data demonstrate that CCR7 controls cortical actin flows, whereas integrins mediate substrate friction that is sufficient to drive locomotion in the absence of considerable surface adhesions and plasma membrane flux.

Cytokinesis in vertebrate cells initiates by contraction of an equatorial actomyosin network composed of randomly oriented filaments - Spira, Felix; Cuylen Haering, Sara; Mehta, Shalin; Samwer, Matthias; Reversat, Anne; Verma, Amitabh; Oldenbourg, Rudolf; Sixt, Michael K; Gerlich, Daniel (eLife)
The actomyosin ring generates force to ingress the cytokinetic cleavage furrow in animal cells, yet its filament organization and the mechanism of contractility is not well understood. We quantified actin filament order in human cells using fluorescence polarization microscopy and found that cleavage furrow ingression initiates by contraction of an equatorial actin network with randomly oriented filaments. The network subsequently gradually reoriented actin filaments along the cell equator. This strictly depended on myosin II activity, suggesting local network reorganization by mechanical forces. Cortical laser microsurgery revealed that during cytokinesis progression, mechanical tension increased substantially along the direction of the cell equator, while the network contracted laterally along the pole-to-pole axis without a detectable increase in tension. Our data suggest that an asymmetric increase in cortical tension promotes filament reorientation along the cytokinetic cleavage furrow, which might have implications for diverse other biological processes involving actomyosin rings.

Migrating platelets are mechano scavengers that collect and bundle bacteria - Gärtner, Florian R; Ahmad, Zerkah; Rosenberger, Gerhild; Fan, Shuxia; Nicolai, Leo; Busch, Benjamin; Yavuz, Gökce; Luckner, Manja; Ishikawa Ankerhold, Hellen; Hennel, Roman; Benechet, Alexandre; Lorenz, Michael; et al. (Cell Press)
Blood platelets are critical for hemostasis and thrombosis and play diverse roles during immune responses. Despite these versatile tasks in mammalian biology, their skills on a cellular level are deemed limited, mainly consisting in rolling, adhesion, and aggregate formation. Here, we identify an unappreciated asset of platelets and show that adherent platelets use adhesion receptors to mechanically probe the adhesive substrate in their local microenvironment. When actomyosin-dependent traction forces overcome substrate resistance, platelets migrate and pile up the adhesive substrate together with any bound particulate material. They use this ability to act as cellular scavengers, scanning the vascular surface for potential invaders and collecting deposited bacteria. Microbe collection by migrating platelets boosts the activity of professional phagocytes, exacerbating inflammatory tissue injury in sepsis. This assigns platelets a central role in innate immune responses and identifies them as potential targets to dampen inflammatory tissue damage in clinical scenarios of severe systemic infection. In addition to their role in thrombosis and hemostasis, platelets can also migrate to sites of infection to help trap bacteria and clear the vascular surface.

FMNL formins boost lamellipodial force generation - Kage, Frieda; Winterhoff, Moritz; Dimchev, Vanessa; Müller, Jan; Thalheim, Tobias; Freise, Anika; Brühmann, Stefan; Kollasser, Jana; Block, Jennifer; Dimchev, Georgi A; Geyer, Matthias; Schnittler, Hams; et al. (Nature Communications)
Migration frequently involves Rac-mediated protrusion of lamellipodia, formed by Arp2/3 complex-dependent branching thought to be crucial for force generation and stability of these networks. The formins FMNL2 and FMNL3 are Cdc42 effectors targeting to the lamellipodium tip and shown here to nucleate and elongate actin filaments with complementary activities in vitro. In migrating B16-F1 melanoma cells, both formins contribute to the velocity of lamellipodium protrusion. Loss of FMNL2/3 function in melanoma cells and fibroblasts reduces lamellipodial width, actin filament density and -bundling, without changing patterns of Arp2/3 complex incorporation. Strikingly, in melanoma cells, FMNL2/3 gene inactivation almost completely abolishes protrusion forces exerted by lamellipodia and modifies their ultrastructural organization. Consistently, CRISPR/Cas-mediated depletion of FMNL2/3 in fibroblasts reduces both migration and capability of cells to move against viscous media. Together, we conclude that force generation in lamellipodia strongly depends on FMNL formin activity, operating in addition to Arp2/3 complex-dependent filament branching.

Multiple roles of filopodial dynamics in particle capture and phagocytosis and phenotypes of Cdc42 and Myo10 deletion - Horsthemke, Markus; Bachg, Anne; Groll, Katharina; Moyzio, Sven; Müther, Barbara; Hemkemeyer, Sandra; Wedlich Söldner, Roland; Sixt, Michael K; Tacke, Sebastian; Bähler, Martin; Hanley, Peter (Journal of Biological Chemistry)
Macrophage filopodia, finger-like membrane protrusions, were first implicated in phagocytosis more than 100 years ago, but little is still known about the involvement of these actin-dependent structures in particle clearance. Using spinning disk confocal microscopy to image filopodial dynamics in mouse resident Lifeact-EGFP macrophages, we show that filopodia, or filopodia-like structures, support pathogen clearance by multiple means. Filopodia supported the phagocytic uptake of bacterial (Escherichia coli) particles by (i) capturing along the filopodial shaft and surfing toward the cell body, the most common mode of capture; (ii) capturing via the tip followed by retraction; (iii) combinations of surfing and retraction; or (iv) sweeping actions. In addition, filopodia supported the uptake of zymosan (Saccharomyces cerevisiae) particles by (i) providing fixation, (ii) capturing at the tip and filopodia-guided actin anterograde flow with phagocytic cup formation, and (iii) the rapid growth of new protrusions. To explore the role of filopodia-inducing Cdc42, we generated myeloid-restricted Cdc42 knock-out mice. Cdc42-deficient macrophages exhibited rapid phagocytic cup kinetics, but reduced particle clearance, which could be explained by the marked rounded-up morphology of these cells. Macrophages lacking Myo10, thought to act downstream of Cdc42, had normal morphology, motility, and phagocytic cup formation, but displayed markedly reduced filopodia formation. In conclusion, live-cell imaging revealed multiple mechanisms involving macrophage filopodia in particle capture and engulfment. Cdc42 is not critical for filopodia or phagocytic cup formation, but plays a key role in driving macrophage lamellipodial spreading.

Locally triggered release of the chemokine CCL21 promotes dendritic cell transmigration across lymphatic endothelia - Vaahtomeri, Kari; Brown, Markus; Hauschild, Robert; De Vries, Ingrid; Leithner, Alexander F; Mehling, Matthias; Kaufmann, Walter; Sixt, Michael K (Cell Reports)
Trafficking cells frequently transmigrate through epithelial and endothelial monolayers. How monolayers cooperate with the penetrating cells to support their transit is poorly understood. We studied dendritic cell (DC) entry into lymphatic capillaries as a model system for transendothelial migration. We find that the chemokine CCL21, which is the decisive guidance cue for intravasation, mainly localizes in the trans-Golgi network and intracellular vesicles of lymphatic endothelial cells. Upon DC transmigration, these Golgi deposits disperse and CCL21 becomes extracellularly enriched at the sites of endothelial cell-cell junctions. When we reconstitute the transmigration process in vitro, we find that secretion of CCL21-positive vesicles is triggered by a DC contact-induced calcium signal, and selective calcium chelation in lymphatic endothelium attenuates transmigration. Altogether, our data demonstrate a chemokine-mediated feedback between DCs and lymphatic endothelium, which facilitates transendothelial migration.

Dendritic cells interpret haptotactic chemokine gradients in a manner governed by signal to noise ratio and dependent on GRK6 - Schwarz, Jan; Bierbaum, Veronika; Vaahtomeri, Kari; Hauschild, Robert; Brown, Markus; De Vries, Ingrid; Leithner, Alexander F; Reversat, Anne; Merrin, Jack; Tarrant, Teresa; Bollenbach, Tobias; Sixt, Michael K (Current Biology)
Navigation of cells along gradients of guidance cues is a determining step in many developmental and immunological processes. Gradients can either be soluble or immobilized to tissues as demonstrated for the haptotactic migration of dendritic cells (DCs) toward higher concentrations of immobilized chemokine CCL21. To elucidate how gradient characteristics govern cellular response patterns, we here introduce an in vitro system allowing to track migratory responses of DCs to precisely controlled immobilized gradients of CCL21. We find that haptotactic sensing depends on the absolute CCL21 concentration and local steepness of the gradient, consistent with a scenario where DC directionality is governed by the signal-to-noise ratio of CCL21 binding to the receptor CCR7. We find that the conditions for optimal DC guidance are perfectly provided by the CCL21 gradients we measure in vivo. Furthermore, we find that CCR7 signal termination by the G-protein-coupled receptor kinase 6 (GRK6) is crucial for haptotactic but dispensable for chemotactic CCL21 gradient sensing in vitro and confirm those observations in vivo. These findings suggest that stable, tissue-bound CCL21 gradients as sustainable “roads” ensure optimal guidance in vivo.

The INO80 complex removes H2A.Z to promote presynaptic filament formation during homologous recombination - Lademann, Claudio; Renkawitz, Jörg; Pfander, Boris; Jentsch, Stefan (Cell Reports)
The INO80 complex (INO80-C) is an evolutionarily conserved nucleosome remodeler that acts in transcription, replication, and genome stability. It is required for resistance against genotoxic agents and is involved in the repair of DNA double-strand breaks (DSBs) by homologous recombination (HR). However, the causes of the HR defect in INO80-C mutant cells are controversial. Here, we unite previous findings using a system to study HR with high spatial resolution in budding yeast. We find that INO80-C has at least two distinct functions during HR—DNA end resection and presynaptic filament formation. Importantly, the second function is linked to the histone variant H2A.Z. In the absence of H2A.Z, presynaptic filament formation and HR are restored in INO80-C-deficient mutants, suggesting that presynaptic filament formation is the crucial INO80-C function during HR.

A dual phenotype of MDA MB 468 cancer cells reveals mutual regulation of tensin3 and adhesion plasticity - Veß, Astrid; Blache, Ulrich; Leitner, Laura; Kurz, Angela; Ehrenpfordt, Anja; Sixt, Michael K; Posern, Guido (Journal of Cell Science)
A change regarding the extent of adhesion - hereafter referred to as adhesion plasticity - between adhesive and less-adhesive states of mammalian cells is important for their behavior. To investigate adhesion plasticity, we have selected a stable isogenic subpopulation of human MDA-MB-468 breast carcinoma cells growing in suspension. These suspension cells are unable to re-adhere to various matrices or to contract three-dimensional collagen lattices. By using transcriptome analysis, we identified the focal adhesion protein tensin3 (Tns3) as a determinant of adhesion plasticity. Tns3 is strongly reduced at mRNA and protein levels in suspension cells. Furthermore, by transiently challenging breast cancer cells to grow under non-adherent conditions markedly reduces Tns3 protein expression, which is regained upon re-adhesion. Stable knockdown of Tns3 in parental MDA-MB-468 cells results in defective adhesion, spreading and migration. Tns3-knockdown cells display impaired structure and dynamics of focal adhesion complexes as determined by immunostaining. Restoration of Tns3 protein expression in suspension cells partially rescues adhesion and focal contact composition. Our work identifies Tns3 as a crucial focal adhesion component regulated by, and functionally contributing to, the switch between adhesive and non-adhesive states in MDA-MB-468 cancer cells.

Cell migration: Making the waves - Müller, Jan; Sixt, Michael K (Current Biology)
Coordinated changes of cell shape are often the result of the excitable, wave-like dynamics of the actin cytoskeleton. New work shows that, in migrating cells, protrusion waves arise from mechanochemical crosstalk between adhesion sites, membrane tension and the actin protrusive machinery.

Load adaptation of lamellipodial actin networks - Mueller, Jan; Szep, Gregory; Nemethova, Maria; De Vries, Ingrid; Lieber, Arnon; Winkler, Christoph; Kruse, Karsten; Small, John; Schmeiser, Christian; Keren, Kinneret; Hauschild, Robert; Sixt, Michael K (Cell)
Actin filaments polymerizing against membranes power endocytosis, vesicular traffic, and cell motility. In vitro reconstitution studies suggest that the structure and the dynamics of actin networks respond to mechanical forces. We demonstrate that lamellipodial actin of migrating cells responds to mechanical load when membrane tension is modulated. In a steady state, migrating cell filaments assume the canonical dendritic geometry, defined by Arp2/3-generated 70° branch points. Increased tension triggers a dense network with a broadened range of angles, whereas decreased tension causes a shift to a sparse configuration dominated by filaments growing perpendicularly to the plasma membrane. We show that these responses emerge from the geometry of branched actin: when load per filament decreases, elongation speed increases and perpendicular filaments gradually outcompete others because they polymerize the shortest distance to the membrane, where they are protected from capping. This network-intrinsic geometrical adaptation mechanism tunes protrusive force in response to mechanical load.

The dynamic cytokine niche - Assen, Frank P; Sixt, Michael K (Immunity)
Immune cells communicate using cytokine signals, but the quantitative rules of this communication aren't clear. In this issue of Immunity, Oyler-Yaniv et al. (2017) suggest that the distribution of a cytokine within a lymphatic organ is primarily governed by the local density of cells consuming it.

The RNA-binding protein tristetraprolin schedules apoptosis of pathogen-engaged neutrophils during bacterial infection - Ebner, Florian; Sedlyarov, Vitaly; Tasciyan, Saren; Ivin, Masa; Kratochvill, Franz; Gratz, Nina; Kenner, Lukas; Villunger, Andreas; Sixt, Michael K; Kovarik, Pavel (The Journal of Clinical Investigation)
Protective responses against pathogens require a rapid mobilization of resting neutrophils and the timely removal of activated ones. Neutrophils are exceptionally short-lived leukocytes, yet it remains unclear whether the lifespan of pathogen-engaged neutrophils is regulated differently from that in the circulating steady-state pool. Here, we have found that under homeostatic conditions, the mRNA-destabilizing protein tristetraprolin (TTP) regulates apoptosis and the numbers of activated infiltrating murine neutrophils but not neutrophil cellularity. Activated TTP-deficient neutrophils exhibited decreased apoptosis and enhanced accumulation at the infection site. In the context of myeloid-specific deletion of Ttp, the potentiation of neutrophil deployment protected mice against lethal soft tissue infection with Streptococcus pyogenes and prevented bacterial dissemination. Neutrophil transcriptome analysis revealed that decreased apoptosis of TTP-deficient neutrophils was specifically associated with elevated expression of myeloid cell leukemia 1 (Mcl1) but not other antiapoptotic B cell leukemia/ lymphoma 2 (Bcl2) family members. Higher Mcl1 expression resulted from stabilization of Mcl1 mRNA in the absence of TTP. The low apoptosis rate of infiltrating TTP-deficient neutrophils was comparable to that of transgenic Mcl1-overexpressing neutrophils. Our study demonstrates that posttranscriptional gene regulation by TTP schedules the termination of the antimicrobial engagement of neutrophils. The balancing role of TTP comes at the cost of an increased risk of bacterial infections.

RASGRP1 deficiency causes immunodeficiency with impaired cytoskeletal dynamics - Salzer, Elisabeth; Çaǧdaş, Deniz; Hons, Miroslav; Mace, Emily; Garncarz, Wojciech; Petronczki, Oezlem; Platzer, René; Pfajfer, Laurène; Bilic, Ivan; Ban, Sol; Willmann, Katharina; Mukherjee, Malini; et al. (Nature Immunology)
RASGRP1 is an important guanine nucleotide exchange factor and activator of the RAS-MAPK pathway following T cell antigen receptor (TCR) signaling. The consequences of RASGRP1 mutations in humans are unknown. In a patient with recurrent bacterial and viral infections, born to healthy consanguineous parents, we used homozygosity mapping and exome sequencing to identify a biallelic stop-gain variant in RASGRP1. This variant segregated perfectly with the disease and has not been reported in genetic databases. RASGRP1 deficiency was associated in T cells and B cells with decreased phosphorylation of the extracellular-signal-regulated serine kinase ERK, which was restored following expression of wild-type RASGRP1. RASGRP1 deficiency also resulted in defective proliferation, activation and motility of T cells and B cells. RASGRP1-deficient natural killer (NK) cells exhibited impaired cytotoxicity with defective granule convergence and actin accumulation. Interaction proteomics identified the dynein light chain DYNLL1 as interacting with RASGRP1, which links RASGRP1 to cytoskeletal dynamics. RASGRP1-deficient cells showed decreased activation of the GTPase RhoA. Treatment with lenalidomide increased RhoA activity and reversed the migration and activation defects of RASGRP1-deficient lymphocytes.

Heme drives hemolysis-induced susceptibility to infection via disruption of phagocyte functions - Martins, Rui; Maier, Julia; Gorki, Anna; Huber, Kilian; Sharif, Omar; Starkl, Philipp; Saluzzo, Simona; Quattrone, Federica; Gawish, Riem; Lakovits, Karin; Aichinger, Michael; Radic Sarikas, Branka; et al. (Nature Immunology)
Hemolysis drives susceptibility to bacterial infections and predicts poor outcome from sepsis. These detrimental effects are commonly considered to be a consequence of heme-iron serving as a nutrient for bacteria. We employed a Gram-negative sepsis model and found that elevated heme levels impaired the control of bacterial proliferation independently of heme-iron acquisition by pathogens. Heme strongly inhibited phagocytosis and the migration of human and mouse phagocytes by disrupting actin cytoskeletal dynamics via activation of the GTP-binding Rho family protein Cdc42 by the guanine nucleotide exchange factor DOCK8. A chemical screening approach revealed that quinine effectively prevented heme effects on the cytoskeleton, restored phagocytosis and improved survival in sepsis. These mechanistic insights provide potential therapeutic targets for patients with sepsis or hemolytic disorders.

A Radical Break Restraining Neutrophil Migration - Renkawitz, Jörg; Sixt, Michael K (Developmental Cell)
When neutrophils infiltrate a site of inflammation, they have to stop at the right place to exert their effector function. In this issue of Developmental Cell, Wang et al. (2016) show that neutrophils sense reactive oxygen species via the TRPM2 channel to arrest migration at their target site. © 2016 Elsevier Inc.

A microfluidic device for measuring cell migration towards substrate bound and soluble chemokine gradients - Schwarz, Jan; Bierbaum, Veronika; Merrin, Jack; Frank, Tino; Hauschild, Robert; Bollenbach, Mark Tobias; Tay, Savaş; Sixt, Michael K; Mehling, Matthias (Scientific Reports)
Cellular locomotion is a central hallmark of eukaryotic life. It is governed by cell-extrinsic molecular factors, which can either emerge in the soluble phase or as immobilized, often adhesive ligands. To encode for direction, every cue must be present as a spatial or temporal gradient. Here, we developed a microfluidic chamber that allows measurement of cell migration in combined response to surface immobilized and soluble molecular gradients. As a proof of principle we study the response of dendritic cells to their major guidance cues, chemokines. The majority of data on chemokine gradient sensing is based on in vitro studies employing soluble gradients. Despite evidence suggesting that in vivo chemokines are often immobilized to sugar residues, limited information is available how cells respond to immobilized chemokines. We tracked migration of dendritic cells towards immobilized gradients of the chemokine CCL21 and varying superimposed soluble gradients of CCL19. Differential migratory patterns illustrate the potential of our setup to quantitatively study the competitive response to both types of gradients. Beyond chemokines our approach is broadly applicable to alternative systems of chemo- and haptotaxis such as cells migrating along gradients of adhesion receptor ligands vs. any soluble cue.

Formin’ a nuclear protection - Renkawitz, Jörg; Sixt, Michael K (Cell)
In this issue of Cell, Skau et al. show that the formin FMN2 organizes a perinuclear actin cytoskeleton that protects the nucleus and its genomic content of migrating cells squeezing through small spaces.

Efficient T-cell priming and activation requires signaling through prostaglandin E2 (EP) receptors - Sreeramkumar, Vinatha; Hons, Miroslav; Punzón, Carmen; Stein, Jens; Sancho, David; Fresno Forcelledo, Manuel; Cuesta, Natalia (Immunology and Cell Biology)
Understanding the regulation of T-cell responses during inflammation and auto-immunity is fundamental for designing efficient therapeutic strategies against immune diseases. In this regard, prostaglandin E 2 (PGE 2) is mostly considered a myeloid-derived immunosuppressive molecule. We describe for the first time that T cells secrete PGE 2 during T-cell receptor stimulation. In addition, we show that autocrine PGE 2 signaling through EP receptors is essential for optimal CD4 + T-cell activation in vitro and in vivo, and for T helper 1 (Th1) and regulatory T cell differentiation. PGE 2 was found to provide additive co-stimulatory signaling through AKT activation. Intravital multiphoton microscopy showed that triggering EP receptors in T cells is also essential for the stability of T cell-dendritic cell (DC) interactions and Th-cell accumulation in draining lymph nodes (LNs) during inflammation. We further demonstrated that blocking EP receptors in T cells during the initial phase of collagen-induced arthritis in mice resulted in a reduction of clinical arthritis. This could be attributable to defective T-cell activation, accompanied by a decline in activated and interferon-γ-producing CD4 + Th1 cells in draining LNs. In conclusion, we prove that T lymphocytes secret picomolar concentrations of PGE 2, which in turn provide additive co-stimulatory signaling, enabling T cells to attain a favorable activation threshold. PGE 2 signaling in T cells is also required for maintaining long and stable interactions with DCs within LNs. Blockade of EP receptors in vivo impairs T-cell activation and development of T cell-mediated inflammatory responses. This may have implications in various pathophysiological settings.

Focal adhesion-independent cell migration - Paluch, Ewa; Aspalter, Irene; Sixt, Michael K (Annual Review of Cell and Developmental Biology)
Cell migration is central to a multitude of physiological processes, including embryonic development, immune surveillance, and wound healing, and deregulated migration is key to cancer dissemination. Decades of investigations have uncovered many of the molecular and physical mechanisms underlying cell migration. Together with protrusion extension and cell body retraction, adhesion to the substrate via specific focal adhesion points has long been considered an essential step in cell migration. Although this is true for cells moving on two-dimensional substrates, recent studies have demonstrated that focal adhesions are not required for cells moving in three dimensions, in which confinement is sufficient to maintain a cell in contact with its substrate. Here, we review the investigations that have led to challenging the requirement of specific adhesions for migration, discuss the physical mechanisms proposed for cell body translocation during focal adhesion-independent migration, and highlight the remaining open questions for the future.

Intralymphatic CCL21 promotes tissue egress of dendritic cells through afferent lymphatic vessels - Russo, Erica; Teijeira, Alvaro; Vaahtomeri, Kari; Willrodt, Ann; Bloch, Joël; Nitschké, Maximilian; Santambrogio, Laura; Kerjaschki, Dontscho; Sixt, Michael K; Halin, Cornelia (Cell Reports)
To induce adaptive immunity, dendritic cells (DCs) migrate through afferent lymphatic vessels (LVs) to draining lymph nodes (dLNs). This process occurs in several consecutive steps. Upon entry into lymphatic capillaries, DCs first actively crawl into downstream collecting vessels. From there, they are next passively and rapidly transported to the dLN by lymph flow. Here, we describe a role for the chemokine CCL21 in intralymphatic DC crawling. Performing time-lapse imaging in murine skin, we found that blockade of CCL21-but not the absence of lymph flow-completely abolished DC migration from capillaries toward collecting vessels and reduced the ability of intralymphatic DCs to emigrate from skin. Moreover, we found that in vitro low laminar flow established a CCL21 gradient along lymphatic endothelial monolayers, thereby inducing downstream-directed DC migration. These findings reveal a role for intralymphatic CCL21 in promoting DC trafficking to dLNs, through the formation of a flow-induced gradient.

Polysialylation controls dendritic cell trafficking by regulating chemokine recognition - Kiermaier, Eva; Moussion, Christine; Veldkamp, Christopher; Gerardy Schahn, Rita; De Vries, Ingrid; Williams, Larry; Chaffee, Gary; Phillips, Andrew; Freiberger, Friedrich; Imre, Richard; Taleski, Deni; Payne, Richard; et al. (Science)
The addition of polysialic acid to N- and/or O-linked glycans, referred to as polysialylation, is a rare posttranslational modification that is mainly known to control the developmental plasticity of the nervous system. Here we show that CCR7, the central chemokine receptor controlling immune cell trafficking to secondary lymphatic organs, carries polysialic acid. This modification is essential for the recognition of the CCR7 ligand CCL21. As a consequence, dendritic cell trafficking is abrogated in polysialyltransferase-deficient mice, manifesting as disturbed lymph node homeostasis and unresponsiveness to inflammatory stimuli. Structure-function analysis of chemokine-receptor interactions reveals that CCL21 adopts an autoinhibited conformation, which is released upon interaction with polysialic acid. Thus, we describe a glycosylation-mediated immune cell trafficking disorder and its mechanistic basis.

Quantitative analysis of dendritic cell haptotaxis - Schwarz, Jan; Sixt, Michael K (Methods in Enzymology)
Chemokines are the main guidance cues directing leukocyte migration. Opposed to early assumptions, chemokines do not necessarily act as soluble cues but are often immobilized within tissues, e.g., dendritic cell migration toward lymphatic vessels is guided by a haptotactic gradient of the chemokine CCL21. Controlled assay systems to quantitatively study haptotaxis in vitro are still missing. In this chapter, we describe an in vitro haptotaxis assay optimized for the unique properties of dendritic cells. The chemokine CCL21 is immobilized in a bioactive state, using laser-assisted protein adsorption by photobleaching. The cells follow this immobilized CCL21 gradient in a haptotaxis chamber, which provides three dimensionally confined migration conditions.

Quantitative analysis of haptotactic cell migration - Schwarz, Jan
Directed cell migration is a hallmark feature, present in almost all multi-cellular organisms. Despite its importance, basic questions regarding force transduction or directional sensing are still heavily investigated. Directed migration of cells guided by immobilized guidance cues - haptotaxis - occurs in key-processes, such as embryonic development and immunity (Middleton et al., 1997; Nguyen et al., 2000; Thiery, 1984; Weber et al., 2013). Immobilized guidance cues comprise adhesive ligands, such as collagen and fibronectin (Barczyk et al., 2009), or chemokines - the main guidance cues for migratory leukocytes (Middleton et al., 1997; Weber et al., 2013). While adhesive ligands serve as attachment sites guiding cell migration (Carter, 1965), chemokines instruct haptotactic migration by inducing adhesion to adhesive ligands and directional guidance (Rot and Andrian, 2004; Schumann et al., 2010). Quantitative analysis of the cellular response to immobilized guidance cues requires in vitro assays that foster cell migration, offer accurate control of the immobilized cues on a subcellular scale and in the ideal case closely reproduce in vivo conditions. The exploration of haptotactic cell migration through design and employment of such assays represents the main focus of this work. Dendritic cells (DCs) are leukocytes, which after encountering danger signals such as pathogens in peripheral organs instruct naïve T-cells and consequently the adaptive immune response in the lymph node (Mellman and Steinman, 2001). To reach the lymph node from the periphery, DCs follow haptotactic gradients of the chemokine CCL21 towards lymphatic vessels (Weber et al., 2013). Questions about how DCs interpret haptotactic CCL21 gradients have not yet been addressed. The main reason for this is the lack of an assay that offers diverse haptotactic environments, hence allowing the study of DC migration as a response to different signals of immobilized guidance cue. In this work, we developed an in vitro assay that enables us to quantitatively assess DC haptotaxis, by combining precisely controllable chemokine photo-patterning with physically confining migration conditions. With this tool at hand, we studied the influence of CCL21 gradient properties and concentration on DC haptotaxis. We found that haptotactic gradient sensing depends on the absolute CCL21 concentration in combination with the local steepness of the gradient. Our analysis suggests that the directionality of migrating DCs is governed by the signal-to-noise ratio of CCL21 binding to its receptor CCR7. Moreover, the haptotactic CCL21 gradient formed in vivo provides an optimal shape for DCs to recognize haptotactic guidance cue. By reconstitution of the CCL21 gradient in vitro we were also able to study the influence of CCR7 signal termination on DC haptotaxis. To this end, we used DCs lacking the G-protein coupled receptor kinase GRK6, which is responsible for CCL21 induced CCR7 receptor phosphorylation and desensitization (Zidar et al., 2009). We found that CCR7 desensitization by GRK6 is crucial for maintenance of haptotactic CCL21 gradient sensing in vitro and confirm those observations in vivo. In the context of the organism, immobilized haptotactic guidance cues often coincide and compete with soluble chemotactic guidance cues. During wound healing, fibroblasts are exposed and influenced by adhesive cues and soluble factors at the same time (Wu et al., 2012; Wynn, 2008). Similarly, migrating DCs are exposed to both, soluble chemokines (CCL19 and truncated CCL21) inducing chemotactic behavior as well as the immobilized CCL21. To quantitatively assess these complex coinciding immobilized and soluble guidance cues, we implemented our chemokine photo-patterning technique in a microfluidic system allowing for chemotactic gradient generation. To validate the assay, we observed DC migration in competing CCL19/CCL21 environments. Adhesiveness guided haptotaxis has been studied intensively over the last century. However, quantitative studies leading to conceptual models are largely missing, again due to the lack of a precisely controllable in vitro assay. A requirement for such an in vitro assay is that it must prevent any uncontrolled cell adhesion. This can be accomplished by stable passivation of the surface. In addition, controlled adhesion must be sustainable, quantifiable and dose dependent in order to create homogenous gradients. Therefore, we developed a novel covalent photo-patterning technique satisfying all these needs. In combination with a sustainable poly-vinyl alcohol (PVA) surface coating we were able to generate gradients of adhesive cue to direct cell migration. This approach allowed us to characterize the haptotactic migratory behavior of zebrafish keratocytes in vitro. Furthermore, defined patterns of adhesive cue allowed us to control for cell shape and growth on a subcellular scale.

Diversified actin protrusions promote environmental exploration but are dispensable for locomotion of leukocytes - Leithner, Alexander F; Eichner, Alexander; Müller, Jan; Reversat, Anne; Brown, Markus; Schwarz, Jan; Merrin, Jack; De Gorter, David; Schur, Florian; Bayerl, Jonathan; De Vries, Ingrid; Wieser, Stefan; et al. (Nature Cell Biology)
Most migrating cells extrude their front by the force of actin polymerization. Polymerization requires an initial nucleation step, which is mediated by factors establishing either parallel filaments in the case of filopodia or branched filaments that form the branched lamellipodial network. Branches are considered essential for regular cell motility and are initiated by the Arp2/3 complex, which in turn is activated by nucleation-promoting factors of the WASP and WAVE families. Here we employed rapid amoeboid crawling leukocytes and found that deletion of the WAVE complex eliminated actin branching and thus lamellipodia formation. The cells were left with parallel filaments at the leading edge, which translated, depending on the differentiation status of the cell, into a unipolar pointed cell shape or cells with multiple filopodia. Remarkably, unipolar cells migrated with increased speed and enormous directional persistence, while they were unable to turn towards chemotactic gradients. Cells with multiple filopodia retained chemotactic activity but their migration was progressively impaired with increasing geometrical complexity of the extracellular environment. These findings establish that diversified leading edge protrusions serve as explorative structures while they slow down actual locomotion.

Impact of the cell division cycle on gene circuits - Bierbaum, Veronika; Klumpp, Stefan (Physical Biology)
In growing cells, protein synthesis and cell growth are typically not synchronous, and, thus, protein concentrations vary over the cell division cycle. We have developed a theoretical description of genetic regulatory systems in bacteria that explicitly considers the cell division cycle to investigate its impact on gene expression. We calculate the cell-to-cell variations arising from cells being at different stages in the division cycle for unregulated genes and for basic regulatory mechanisms. These variations contribute to the extrinsic noise observed in single-cell experiments, and are most significant for proteins with short lifetimes. Negative autoregulation buffers against variation of protein concentration over the division cycle, but the effect is found to be relatively weak. Stronger buffering is achieved by an increased protein lifetime. Positive autoregulation can strongly amplify such variation if the parameters are set to values that lead to resonance-like behaviour. For cooperative positive autoregulation, the concentration variation over the division cycle diminishes the parameter region of bistability and modulates the switching times between the two stable states. The same effects are seen for a two-gene mutual-repression toggle switch. By contrast, an oscillatory circuit, the repressilator, is only weakly affected by the division cycle.

Actin flows mediate a universal coupling between cell speed and cell persistence - Maiuri, Paolo; Rupprecht, Jean; Wieser, Stefan; Ruprecht, Verena; Bénichou, Olivier; Carpi, Nicolas; Coppey, Mathieu; De Beco, Simon; Gov, Nir; Heisenberg, Carl-Philipp J; Lage Crespo, Carolina; Lautenschlaeger, Franziska; et al. (Cell)
Cell movement has essential functions in development, immunity, and cancer. Various cell migration patterns have been reported, but no general rule has emerged so far. Here, we show on the basis of experimental data in vitro and in vivo that cell persistence, which quantifies the straightness of trajectories, is robustly coupled to cell migration speed. We suggest that this universal coupling constitutes a generic law of cell migration, which originates in the advection of polarity cues by an actin cytoskeleton undergoing flows at the cellular scale. Our analysis relies on a theoretical model that we validate by measuring the persistence of cells upon modulation of actin flow speeds and upon optogenetic manipulation of the binding of an actin regulator to actin filaments. Beyond the quantitative prediction of the coupling, the model yields a generic phase diagram of cellular trajectories, which recapitulates the full range of observed migration patterns.

A novel Cre recombinase reporter mouse strain facilitates selective and efficient infection of primary immune cells with adenoviral vectors - Heger, Klaus; Kober, Maike; Rieß, David; Drees, Christoph; De Vries, Ingrid; Bertossi, Arianna; Roers, Axel; Sixt, Michael K; Schmidt Supprian, Marc (European Journal of Immunology)
Replication-deficient recombinant adenoviruses are potent vectors for the efficient transient expression of exogenous genes in resting immune cells. However, most leukocytes are refractory to efficient adenoviral transduction as they lack expression of the coxsackie/adenovirus receptor (CAR). To circumvent this obstacle, we generated the R26/CAG-CARΔ1StopF (where R26 is ROSA26 and CAG is CMV early enhancer/chicken β actin promoter) knock-in mouse line. This strain allows monitoring of in situ Cre recombinase activity through expression of CARΔ1. Simultaneously, CARΔ1 expression permits selective and highly efficient adenoviral transduction of immune cell populations, such as mast cells or T cells, directly ex vivo in bulk cultures without prior cell purification or activation. Furthermore, we show that CARΔ1 expression dramatically improves adenoviral infection of in vitro differentiated conventional and plasmacytoid dendritic cells (DCs), basophils, mast cells, as well as Hoxb8-immortalized hematopoietic progenitor cells. This novel dual function mouse strain will hence be a valuable tool to rapidly dissect the function of specific genes in leukocyte physiology.

The lymph node filter revealed - Hons, Miroslav; Sixt, Michael K (Nature Immunology)
Stromal cells in the subcapsular sinus of the lymph node 'decide' which cells and molecules are allowed access to the deeper parenchyma. The glycoprotein PLVAP is a crucial component of this selector function.

Cell migration and antigen capture are antagonistic processes coupled by myosin II in dendritic cells - Chabaud, Mélanie; Heuzé, Mélina; Bretou, Marine; Vargas, Pablo; Maiuri, Paolo; Solanes, Paola; Maurin, Mathieu; Terriac, Emmanuel; Le Berre, Maël; Lankar, Danielle; Piolot, Tristan; Adelstein, Robert; et al. (Nature Communications)
The immune response relies on the migration of leukocytes and on their ability to stop in precise anatomical locations to fulfil their task. How leukocyte migration and function are coordinated is unknown. Here we show that in immature dendritic cells, which patrol their environment by engulfing extracellular material, cell migration and antigen capture are antagonistic. This antagonism results from transient enrichment of myosin IIA at the cell front, which disrupts the back-to-front gradient of the motor protein, slowing down locomotion but promoting antigen capture. We further highlight that myosin IIA enrichment at the cell front requires the MHC class II-associated invariant chain (Ii). Thus, by controlling myosin IIA localization, Ii imposes on dendritic cells an intermittent antigen capture behaviour that might facilitate environment patrolling. We propose that the requirement for myosin II in both cell migration and specific cell functions may provide a general mechanism for their coordination in time and space.

Editorial overview: Cell adhesion and migration - Sixt, Michael K; Raz, Erez (Current Opinion in Cell Biology)

Navigating in tissue mazes: Chemoattractant interpretation in complex environments - Sarris, Milka; Sixt, Michael K (Current Opinion in Cell Biology)
Guided cell movement is essential for development and integrity of animals and crucially involved in cellular immune responses. Leukocytes are professional migratory cells that can navigate through most types of tissues and sense a wide range of directional cues. The responses of these cells to attractants have been mainly explored in tissue culture settings. How leukocytes make directional decisions in situ, within the challenging environment of a tissue maze, is less understood. Here we review recent advances in how leukocytes sense chemical cues in complex tissue settings and make links with paradigms of directed migration in development and Dictyostelium discoideum amoebae.

Fragmented communication between immune cells: Neutrophils blaze a trail with migratory cues for T cells to follow to sites of infection - Kiermaier, Eva; Sixt, Michael K (Science)

The serotonin receptor 5-HT7R regulates the morphology and migratory properties of dendritic cells - Holst, Katrin; Guseva, Daria; Schindler, Susann; Sixt, Michael K; Braun, Armin; Chopra, Himpriya; Pabst, Oliver; Ponimaskin, Evgeni (Journal of Cell Science)
Dendritic cells are potent antigen-presenting cells endowed with the unique ability to initiate adaptive immune responses upon inflammation. Inflammatory processes are often associated with an increased production of serotonin, which operates by activating specific receptors. However, the functional role of serotonin receptors in regulation of dendritic cell functions is poorly understood. Here, we demonstrate that expression of serotonin receptor 5-HT7 (5-HT7TR) as well as its downstream effector Cdc42 is upregulated in dendritic cells upon maturation. Although dendritic cell maturation was independent of 5-HT7TR, receptor stimulation affected dendritic cell morphology through Cdc42-mediated signaling. In addition, basal activity of 5-HT7TR was required for the proper expression of the chemokine receptor CCR7, which is a key factor that controls dendritic cell migration. Consistent with this, we observed that 5-HT7TR enhances chemotactic motility of dendritic cells in vitro by modulating their directionality and migration velocity. Accordingly, migration of dendritic cells in murine colon explants was abolished after pharmacological receptor inhibition. Our results indicate that there is a crucial role for 5-HT7TR-Cdc42-mediated signaling in the regulation of dendritic cell morphology and motility, suggesting that 5-HT7TR could be a new target for treatment of a variety of inflammatory and immune disorders.

Solution structure of CCL19 and identification of overlapping CCR7 and PSGL-1 binding sites - Veldkamp, Christopher; Kiermaier, Eva; Gabel Eissens, Skylar; Gillitzer, Miranda; Lippner, David; Disilvio, Frank; Mueller, Casey; Wantuch, Paeton; Chaffee, Gary; Famiglietti, Michael; Zgoba, Danielle; Bailey, Asha; et al. (Biochemistry)
CCL19 and CCL21 are chemokines involved in the trafficking of immune cells, particularly within the lymphatic system, through activation of CCR7. Concurrent expression of PSGL-1 and CCR7 in naive T-cells enhances recruitment of these cells to secondary lymphoid organs by CCL19 and CCL21. Here the solution structure of CCL19 is reported. It contains a canonical chemokine domain. Chemical shift mapping shows the N-termini of PSGL-1 and CCR7 have overlapping binding sites for CCL19 and binding is competitive. Implications for the mechanism of PSGL-1's enhancement of resting T-cell recruitment are discussed.

Cortical contractility triggers a stochastic switch to fast amoeboid cell motility - Ruprecht, Verena; Wieser, Stefan; Callan Jones, Andrew; Smutny, Michael; Morita, Hitoshi; Sako, Keisuke; Barone, Vanessa; Ritsch Marte, Monika; Sixt, Michael K; Voituriez, Raphaël; Heisenberg, Carl-Philipp J (Cell)
3D amoeboid cell migration is central to many developmental and disease-related processes such as cancer metastasis. Here, we identify a unique prototypic amoeboid cell migration mode in early zebrafish embryos, termed stable-bleb migration. Stable-bleb cells display an invariant polarized balloon-like shape with exceptional migration speed and persistence. Progenitor cells can be reversibly transformed into stable-bleb cells irrespective of their primary fate and motile characteristics by increasing myosin II activity through biochemical or mechanical stimuli. Using a combination of theory and experiments, we show that, in stable-bleb cells, cortical contractility fluctuations trigger a stochastic switch into amoeboid motility, and a positive feedback between cortical flows and gradients in contractility maintains stable-bleb cell polarization. We further show that rearward cortical flows drive stable-bleb cell migration in various adhesive and non-adhesive environments, unraveling a highly versatile amoeboid migration phenotype.

Physiology: Relax and come in - Sixt, Michael K; Vaahtomeri, Kari (Nature)
During inflammation, lymph nodes swell with an influx of immune cells. New findings identify a signalling pathway that induces relaxation in the contractile cells that give structure to these organs.

Langerhans cell maturation is accompanied by induction of N-cadherin and the transcriptional regulators of epithelial-mesenchymal transition ZEB1/2 - Konradi, Sabine; Yasmin, Nighat; Haslwanter, Denise; Weber, Michele; Gesslbauer, Bernd; Sixt, Michael K; Strobl, Herbert (European Journal of Immunology)
angerhans cells (LCs) are a unique subset of dendritic cells (DCs) that express epithelial adhesion molecules, allowing them to form contacts with epithelial cells and reside in epidermal/epithelial tissues. The dynamic regulation of epithelial adhesion plays a decisive role in the life cycle of LCs. It controls whether LCs remain immature and sessile within the epidermis or mature and egress to initiate immune responses. So far, the molecular machinery regulating epithelial adhesion molecules during LC maturation remains elusive. Here, we generated pure populations of immature human LCs in vitro to systematically probe for gene-expression changes during LC maturation. LCs down-regulate a set of epithelial genes including E-cadherin, while they upregulate the mesenchymal marker N-cadherin known to facilitate cell migration. In addition, N-cadherin is constitutively expressed by monocyte-derived DCs known to exhibit characteristics of both inflammatory-type and interstitial/dermal DCs. Moreover, the transcription factors ZEB1 and ZEB2 (ZEB is zinc-finger E-box-binding homeobox) are upregulated in migratory LCs. ZEB1 and ZEB2 have been shown to induce epithelial-to-mesenchymal transition (EMT) and invasive behavior in cancer cells undergoing metastasis. Our results provide the first hint that the molecular EMT machinery might facilitate LC mobilization. Moreover, our study suggests that N-cadherin plays a role during DC migration.

A single-molecule approach to explore binding uptake and transport of cancer cell targeting nanotubes - Lamprecht, Constanze; Plochberger, Birgit; Ruprecht, Verena; Wieser, Stefan; Rankl, Christian; Heister, Elena; Unterauer, Barbara; Brameshuber, Mario; Danzberger, Jürgen; Lukanov, Petar; Flahaut, Emmanuel; Schütz, Gerhard; et al. (Nanotechnology)
In the past decade carbon nanotubes (CNTs) have been widely studied as a potential drug-delivery system, especially with functionality for cellular targeting. Yet, little is known about the actual process of docking to cell receptors and transport dynamics after internalization. Here we performed single-particle studies of folic acid (FA) mediated CNT binding to human carcinoma cells and their transport inside the cytosol. In particular, we employed molecular recognition force spectroscopy, an atomic force microscopy based method, to visualize and quantify docking of FA functionalized CNTs to FA binding receptors in terms of binding probability and binding force. We then traced individual fluorescently labeled, FA functionalized CNTs after specific uptake, and created a dynamic 'roadmap' that clearly showed trajectories of directed diffusion and areas of nanotube confinement in the cytosol. Our results demonstrate the potential of a single-molecule approach for investigation of drug-delivery vehicles and their targeting capacity.

New paradigms in the establishment and maintenance of gradients during directed cell migration - Majumdar, Ritankar; Sixt, Michael K; Parent, Carole (Current Opinion in Cell Biology)
Directional guidance of migrating cells is relatively well explored in the reductionist setting of cell culture experiments. Here spatial gradients of chemical cues as well as gradients of mechanical substrate characteristics prove sufficient to attract single cells as well as their collectives. How such gradients present and act in the context of an organism is far less clear. Here we review recent advances in understanding how guidance cues emerge and operate in the physiological context.

Blood vessels pattern heparan sulfate gradients between their apical and basolateral aspects - Stoler Barak, Liat; Moussion, Christine; Shezen, Elias; Hatzav, Miki; Sixt, Michael K; Alon, Ronen (PLoS One)
A hallmark of immune cell trafficking is directional guidance via gradients of soluble or surface bound chemokines. Vascular endothelial cells produce, transport and deposit either their own chemokines or chemokines produced by the underlying stroma. Endothelial heparan sulfate (HS) was suggested to be a critical scaffold for these chemokine pools, but it is unclear how steep chemokine gradients are sustained between the lumenal and ablumenal aspects of blood vessels. Addressing this question by semi-quantitative immunostaining of HS moieties around blood vessels with a pan anti-HS IgM mAb, we found a striking HS enrichment in the basal lamina of resting and inflamed post capillary skin venules, as well as in high endothelial venules (HEVs) of lymph nodes. Staining of skin vessels with a glycocalyx probe further suggested that their lumenal glycocalyx contains much lower HS density than their basolateral extracellular matrix (ECM). This polarized HS pattern was observed also in isolated resting and inflamed microvascular dermal cells. Notably, progressive skin inflammation resulted in massive ECM deposition and in further HS enrichment around skin post capillary venules and their associated pericytes. Inflammation-dependent HS enrichment was not compromised in mice deficient in the main HS degrading enzyme, heparanase. Our results suggest that the blood vasculature patterns steep gradients of HS scaffolds between their lumenal and basolateral endothelial aspects, and that inflammatory processes can further enrich the HS content nearby inflamed vessels. We propose that chemokine gradients between the lumenal and ablumenal sides of vessels could be favored by these sharp HS scaffold gradients.

Mechanisms and principles of homology search during recombination - Renkawitz, Jörg; Lademann, Claudio; Jentsch, Stefan (Nature Reviews Molecular Cell Biology)
Homologous recombination is crucial for genome stability and for genetic exchange. Although our knowledge of the principle steps in recombination and its machinery is well advanced, homology search, the critical step of exploring the genome for homologous sequences to enable recombination, has remained mostly enigmatic. However, recent methodological advances have provided considerable new insights into this fundamental step in recombination that can be integrated into a mechanistic model. These advances emphasize the importance of genomic proximity and nuclear organization for homology search and the critical role of homology search mediators in this process. They also aid our understanding of how homology search might lead to unwanted and potentially disease-promoting recombination events.

A miR-155-dependent microRNA hierarchy in dendritic cell maturation and macrophage activation - Dueck, Anne; Eichner, Alexander; Sixt, Michael K; Meister, Gunter (FEBS Letters)
MicroRNAs (miRNAs) are small RNAs that play important regulatory roles in many cellular pathways. MiRNAs associate with members of the Argonaute protein family and bind to partially complementary sequences on mRNAs and induce translational repression or mRNA decay. Using deep sequencing and Northern blotting, we characterized miRNA expression in wild type and miR-155-deficient dendritic cells (DCs) and macrophages. Analysis of different stimuli (LPS, LDL, eLDL, oxLDL) reveals a direct influence of miR-155 on the expression levels of other miRNAs. For example, miR-455 is negatively regulated in miR-155-deficient cells possibly due to inhibition of the transcription factor C/EBPbeta by miR-155. Based on our comprehensive data sets, we propose a model of hierarchical miRNA expression dominated by miR-155 in DCs and macrophages.

A conduit to amplify innate immunity - Moussion, Christine; Sixt, Michael K (Immunity)

Interstitial dendritic cell guidance by haptotactic chemokine gradients - Weber, Michele; Hauschild, Robert; Schwarz, Jan; Moussion, Christine; De Vries, Ingrid; Legler, Daniel; Luther, Sanjiv; Bollenbach, Mark Tobias; Sixt, Michael K (Science)
Directional guidance of cells via gradients of chemokines is considered crucial for embryonic development, cancer dissemination, and immune responses. Nevertheless, the concept still lacks direct experimental confirmation in vivo. Here, we identify endogenous gradients of the chemokine CCL21 within mouse skin and show that they guide dendritic cells toward lymphatic vessels. Quantitative imaging reveals depots of CCL21 within lymphatic endothelial cells and steeply decaying gradients within the perilymphatic interstitium. These gradients match the migratory patterns of the dendritic cells, which directionally approach vessels from a distance of up to 90-micrometers. Interstitial CCL21 is immobilized to heparan sulfates, and its experimental delocalization or swamping the endogenous gradients abolishes directed migration. These findings functionally establish the concept of haptotaxis, directed migration along immobilized gradients, in tissues.

Thymic medullar conduits-associated podoplanin promotes natural regulatory T cells - Fuertbauer, Elke; Zaujec, Jan; Uhrin, Pavel; Raab, Ingrid; Weber, Michele; Schachner, Helga; Bauer, Miroslav; Schütz, Gerhard; Binder, Bernd; Sixt, Michael K; Kerjaschki, Dontscho; Stockinger, Hannes (Immunology Letters)
Podoplanin, a mucin-like plasma membrane protein, is expressed by lymphatic endothelial cells and responsible for separation of blood and lymphatic circulation through activation of platelets. Here we show that podoplanin is also expressed by thymic fibroblastic reticular cells (tFRC), a novel thymic medulla stroma cell type associated with thymic conduits, and involved in development of natural regulatory T cells (nTreg). Young mice deficient in podoplanin lack nTreg owing to retardation of CD4+CD25+ thymocytes in the cortex and missing differentiation of Foxp3+ thymocytes in the medulla. This might be due to CCL21 that delocalizes upon deletion of the CCL21-binding podoplanin from medullar tFRC to cortex areas. The animals do not remain devoid of nTreg but generate them delayed within the first month resulting in Th2-biased hypergammaglobulinemia but not in the death-causing autoimmune phenotype of Foxp3-deficient Scurfy mice.

Live Cell Imaging of Chemotactic Dendritic Cell Migration in Explanted Mouse Ear Preparations - Weber, Michele; Sixt, Michael K (Chemokines)
Leukocyte migration through the interstitial space is crucial for the maintenance of tolerance and immunity. The main cues for leukocyte trafficking are chemokines thought to directionally guide these cells towards their targets. However, model systems that facilitate quantification of chemokine-guided leukocyte migration in vivo are uncommon. Here we describe an ex vivo crawl-in assay using explanted mouse ears that allows the visualization of chemokine-dependent dendritic cell (DC) motility in the dermal interstitium in real time. We present methods for the preparation of mouse ear sheets and their use in multidimensional confocal imaging experiments to monitor and analyze the directional migration of fluorescently labelled DCs through the dermis and into afferent lymphatic vessels. The assay provides a more physiological approach to study leukocyte migration than in vitro three-dimensional (3D) or 2-dimensional (2D) migration assays such as collagen gels and transwell assays.

MicroRNAs associated with the different human Argonaute proteins - Dueck, Anne; Ziegler, Christian; Eichner, Alexander; Berezikov, Eugène; Meister, Gunter (Nucleic Acids Research)
MicroRNAs (miRNAs) are small noncoding RNAs that function in literally all cellular processes. miRNAs interact with Argonaute (Ago) proteins and guide them to specific target sites located in the 3′-untranslated region (3′-UTR) of target mRNAs leading to translational repression and deadenylation-induced mRNA degradation. Most miRNAs are processed from hairpin-structured precursors by the consecutive action of the RNase III enzymes Drosha and Dicer. However, processing of miR-451 is Dicer independent and cleavage is mediated by the endonuclease Ago2. Here we have characterized miR-451 sequence and structure requirements for processing as well as sorting of miRNAs into different Ago proteins. Pre-miR-451 appears to be optimized for Ago2 cleavage and changes result in reduced processing. In addition, we show that the mature miR-451 only associates with Ago2 suggesting that mature miRNAs are not exchanged between different members of the Ago protein family. Based on cloning and deep sequencing of endogenous miRNAs associated with Ago1-3, we do not find evidence for miRNA sorting in human cells. However, Ago identity appears to influence the length of some miRNAs, while others remain unaffected.

HEVs, lymphatics and homeostatic immune cell trafficking in lymph nodes - Girard, Jean; Moussion, Christine; Förster, Reinhold (Nature Reviews Immunology)
In search of foreign antigens, lymphocytes recirculate from the blood, through lymph nodes, into lymphatics and back to the blood. Dendritic cells also migrate to lymph nodes for optimal interaction with lymphocytes. This continuous trafficking of immune cells into and out of lymph nodes is essential for immune surveillance of foreign invaders. In this article, we review our current understanding of the functions of high endothelial venules (HEVs), stroma and lymphatics in the entry, positioning and exit of immune cells in lymph nodes during homeostasis, and we highlight the unexpected role of dendritic cells in the control of lymphocyte homing through HEVs.

NextGen speaks 13 - Weber, Michele (Science)